Lithium-ion secondary battery, battery device, power-consuming device, method for producing positive electrode active material, and method for producing positive electrode sheet
Patent Information
- Application Number
- CN202510614623.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-29
- Filing Date
- 2025-05-13
- Publication Date
- 2026-10-30
AI Technical Summary
随着市场对含锂过渡金属磷酸盐体系二次电池能量密度和循环性能要求的提高,现有技术中难以同时实现上述性能的同时改善,这成为本领域亟须解决的技术问题
[0073]上述说明仅是本申请技术方案的概述,为了能够更清楚了解本申请的技术手段,而可依照说明书的内容予以实施,并且为了让本申请的上述和其他目的、特征和优点能够更明显易懂,以下特举本申请的具体实施方式。
Smart Images

Figure CN123017889A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion secondary battery technology, and in particular to a lithium-ion secondary battery, battery device, power supply device, a method for preparing positive electrode active material, and a method for preparing positive electrode sheet. Background Technology
[0002] In recent years, lithium-ion secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric cars, military equipment, and aerospace.
[0003] Positive electrode active materials are an important component of secondary batteries. Lithium-containing transition metal phosphate materials have the characteristics of structural stability, good safety, and long cycle life, and have broad development prospects. As the market demands higher energy density and cycle performance from lithium-containing transition metal phosphate system secondary batteries, it is difficult to simultaneously improve these properties using existing technologies. This has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0004] In view of the above problems, this application provides a method for preparing a battery cell, a battery device, an electrical device, a positive electrode active material, and a method for preparing a positive electrode sheet, which are described below.
[0005] The first aspect of this application provides a lithium-ion secondary battery, comprising a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive current collector and a positive electrode film disposed on at least one side of the positive current collector. The positive electrode film includes a positive active material, comprising lithium transition metal phosphate particles with at least a carbon coating on their surface. Based on the total area of particles in a cross-section along the thickness direction of the positive electrode film, the area percentage of particles with a particle size R1 satisfying 1.5 μm ≤ R1 < 5 μm is 10.0%-20.0%, the area percentage of particles with a particle size R2 satisfying 50 nm ≤ R2 < 200 nm is 5.0%-12.0%, and the area percentage of particles with a particle size R3 satisfying 200 nm ≤ R3 < 1.5 μm is 73.0%-80.0%. The particle size distribution (D) of particles with a particle size R3 is... A90 -D A10 ) / D A50 The range is 1.40-1.683.
[0006] In this embodiment, the positive electrode sheet achieves the following by controlling the area ratio of particles with diameter R1 satisfying 1.5μm≤R1<5μm to be 10.0%-20.0%, particles with diameter R2 satisfying 50nm≤R2<200nm to be 5.0%-12.0%, and particles with diameter R3 satisfying 200nm≤R3<1.5μm to be 73.0%-80.0%. The particle size distribution (D) of particles satisfying diameter R3 is also controlled. A90 -D A10 ) / D A50 A particle size distribution of 1.40-1.683 helps improve the uniformity of lithium-ion diffusion rates and reduces the overall specific surface area difference of particles within the film, allowing for more uniform contact with lithium-ions in the electrolyte, thereby improving the battery's ion conductivity and stability. Simultaneously, a certain particle size gradient is formed within the R3 particles. Through the synergistic effect of particles of different sizes, the interlocking effect between particles is optimized, effectively reducing the overall porosity. The entire packing system achieves a more compact arrangement, thus significantly improving the compaction density. In this gradation, particles of different sizes also have complementary properties in stress distribution and inter-particle interactions, enabling the material to increase overall stability under external pressure through mechanical interlocking, achieving a balance between energy density and cycle performance.
[0007] In any embodiment, the area ratio of particles with a particle size R3 satisfying 200nm≤R3<1.5μm is 74.0%-78.0%.
[0008] In the positive electrode film, particles with a diameter R3 satisfying 200nm ≤ R3 < 1.5μm are easier to fill gaps than particles with a diameter greater than or equal to 1.5μm, achieving a higher packing density. Compared to particles with a diameter less than 200nm, their larger volume provides better support for the large particle packing framework, reducing the possibility of deformation or stress concentration due to expansion or external forces, thus improving structural stability. Therefore, a particle area ratio of 200nm or greater and less than 1.5μm within this range can further improve the compaction density and structural strength of the entire particle system, thereby increasing the battery's energy density and cycle performance.
[0009] In any embodiment, the area percentage of particles with a particle size R2 satisfying 50nm≤R2<200nm is 6.00%-10.00%.
[0010] Since the area of a single particle with a particle size R2 satisfying 50nm≤R2<200nm is small, it can effectively fill the gaps between particles, thereby improving the stacking structure and density of the electrode; the overall area ratio of particles within this particle size range is small, which at the same time reduces the probability of side reactions and improves the cycle performance of the battery.
[0011] In any embodiment, the area ratio of particles with a particle size R1 satisfying 1.5μm≤R1<5μm is 13.00%-18.00%.
[0012] In the cross-section of the positive electrode film along the thickness direction of the electrode sheet, particles with a particle size R1 satisfying 1.5μm≤R1<5μm can occupy a certain space in the stacking and provide a structural framework due to their larger particle size and stronger geometric stability. This optimizes the arrangement between particles, further improves the compaction density of the electrode sheet, and improves the energy density of the battery.
[0013] In any embodiment, the median L of the spheroidal density in the cumulative distribution curve of the particle spheroidal density obtained from a cross-section of the positive electrode film along the electrode thickness direction is... A50 The range is 0.70-0.85, with a possible value of 0.70-0.76. The median L of sphericity. A50 Within the aforementioned range, the particles are approximately spherical, which helps them maintain good slidability during stacking, making it easier to fill the gaps between particles. This further improves the compaction density of the electrode and increases the energy density of the battery.
[0014] In any embodiment, the median L of the spheroidity area cumulative distribution curve of particles with a particle size R1 satisfying 1.5μm≤R1<5μm obtained from the cross-section of the positive electrode film along the electrode thickness direction is... R1A50 It is 0.70-0.76.
[0015] The median sphericity of particles with a particle size R1 satisfying 1.5μm≤R1<5μm is within the above range, which effectively improves the problem of poor sphericity of large particles, reduces particle bridging caused by the irregular shape of large particles, and reduces the void content in the electrode sheet; while retaining a certain degree of irregularity, it helps to form a structural network with a certain strength between particles, which can withstand greater rolling pressure and internal and external stress, thus improving the compaction density of the electrode sheet and the energy density of the battery.
[0016] In any embodiment, the median L of the sphericity is obtained from the cumulative distribution curve of the sphericity area of particles with a particle size R2 satisfying 50nm ≤ R2 < 200nm along the cross-section of the positive electrode film along the electrode thickness direction. R2A50 It is 0.73-0.80.
[0017] The median sphericity of particles with a particle size R2 satisfying 50nm≤R2<200nm is within the above range. Small particles have high sphericity, and regularly shaped small particles are beneficial for filling the voids in the electrode sheet, further improving the compaction density of the electrode sheet and the energy density of the battery.
[0018] In any embodiment, the median L of the spheroidal area cumulative distribution curve of particles with a particle size R3 satisfying 200nm ≤ R3 < 1.5μm obtained from the cross-section of the positive electrode film along the electrode thickness direction is the spheroidal area distribution curve. R3A50 It is 0.71-0.77.
[0019] The median sphericity of particles with a particle size R3 satisfying 200nm≤R3<1.5μm is within the above range. Particles with an R3 particle size having the largest area distribution ratio have better sphericity, which is conducive to uniform slip between particles, reduces the probability of local stress concentration, and further improves the compaction density of the electrode.
[0020] In any embodiment, the median R of the roughness of the particles in the cumulative distribution curve of the particle roughness obtained along the thickness direction of the positive electrode film is... A50 It is 0.92-0.96.
[0021] Median roughness R A50 Within the aforementioned range, the particle surface is relatively smooth, and the friction between particles is relatively small. Under the action of external force, it is easy to slip, which can further improve the compaction density of the electrode and increase the energy density of the battery.
[0022] In any embodiment, the median C of the graphitization degree C in the cumulative distribution curve of the positive electrode film obtained in the laser microscopy confocal Raman spectroscopy instrument scanning mode is... 50 The value is 0.98-1.20, and can be selected as 1.02-1.10, where the graphitization degree C value is I. G / I D I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of peak G at I D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.
[0023] The graphitization degree of the particles in the positive electrode film is within the above range, indicating that the proportion of graphitic carbon in the positive electrode film is high. The particles can easily slip by means of the highly graphitized carbon structure in the coating material. Combined with the high sphericity of the particles, it is more conducive to the slippage between particles, thereby improving the compaction density of the electrode sheet.
[0024] In any embodiment, the median B of the coating value B obtained in the cumulative distribution curve of the positive electrode film layer in the laser microscopy confocal Raman spectroscopy instrument scanning mode is... 50 The value is 0.30-0.50, where the coating value B is I. P / I D , where I PThis indicates that the Raman spectrum is at 948±100 cm⁻¹ -1 The intensity of the P peak at I D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.
[0025] The median B of the coating value of the positive electrode film 50 Within the above range, it is indicated that the carbon coating material of the positive electrode active material is relatively dense and uniform, which is beneficial to improving the slippage of the positive electrode film during the rolling process, and further improving the compaction density of the electrode sheet and the energy density of the battery.
[0026] In any embodiment, the carbon content is 0.8%-1.8% based on the total mass of the positive electrode active material, and optionally 0.90%-1.5%.
[0027] This positive electrode active material has a relatively low carbon coating content, which can further increase the loading of lithium transition metal phosphates in the positive electrode sheet and improve the energy density of lithium-ion secondary batteries.
[0028] In any embodiment, the lithium iron ion reverse defect concentration of the positive electrode active material is 0.001%-1.5%, and optionally 0.01%-1.0%.
[0029] During preparation and cycling, lithium vacancies inevitably exist within the crystal structure of the positive electrode active material. These vacancies not only lead to the oxidation of ferrous ions to ferric ions but also induce partial migration of ferric ions to lithium sites, forming lithium-iron antisite defects. This blocks the one-dimensional diffusion channels of lithium ions, adversely affecting the solid-phase transport of lithium ions. The positive electrode active material in this application has low lithium-iron antisite defects, which is beneficial for the uniform transport of lithium ions in the solid phase and can improve the kinetic performance of lithium-ion secondary batteries.
[0030] In any embodiment, the lithium-containing transition metal phosphate particles comprise a component having the following general formula:
[0031] Li m Fe x P y O j Q q ,
[0032] Wherein, Q includes one or more of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, with 0.8≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0≤q≤0.1.
[0033] Selecting an appropriate modifying element Q can improve the ion diffusion pathway of the positive electrode active material, improve the lithium ion diffusion rate of the positive electrode active material, and improve the kinetic performance of the battery.
[0034] In any embodiment, the positive electrode active material includes one or more of lithium iron phosphate and its doped and modified materials, and coated and modified materials.
[0035] In any embodiment, the positive electrode active material includes titanium, and the mass content of titanium is 4000ppm-8000ppm based on the total mass of the positive electrode active material.
[0036] Doping titanium in cathode active materials can induce lattice distortion, reduce Li-O bond energy, increase lithium-ion transport rate, and improve the kinetic performance of lithium-ion secondary batteries. However, in existing technologies, the doping content of titanium in lithium-containing transition metal phosphates often cannot exceed 3000 ppm, because excessive titanium is difficult to completely enter the bulk phase of lithium-containing transition metal phosphates and easily becomes a harmful impurity phase remaining on the surface, negatively impacting battery performance.
[0037] In any embodiment, the tap density of the positive electrode active material is 1.00 g / cm³. 3 -1.70g / cm 3 1.20g / cm³ is an optional value. 3 -1.50g / cm 3 .
[0038] In this embodiment, the positive electrode active material particles, through R3 particles with a certain distribution width, effectively reduce the overall porosity by optimizing the interlocking effect between particles, thus achieving a high tap density.
[0039] In any embodiment, the compacted density of the positive electrode active material under 3T pressure is 2.55 g / cm³. 3 -2.70g / cm 3 The option is 2.58g / cm³. 3 -2.68g / cm 3 .
[0040] The positive electrode active material particles have a good packing structure, so they can achieve a higher compaction density under pressure, providing a material basis for improving the compaction density of the electrode and preparing high-energy-density lithium-ion secondary batteries.
[0041] In any embodiment, the powder resistivity of the positive electrode active material at a pressure of 8 MPa is 0.5 Ω·cm-60.0 Ω·cm, and can be selected as 2.0 Ω·cm-40.0 Ω·cm.
[0042] This positive electrode active material is produced by coating a carbon material on its surface, utilizing the spt properties of the surface carbon. 2 The structure facilitates rapid electron conduction between particles, resulting in low powder resistivity in the positive electrode active material. This is beneficial for improving the solid-phase electron transport rate and enhancing the battery's kinetic performance.
[0043] In any embodiment, the discharge specific capacity of the positive electrode active material at a 1C discharge rate is 135mAh / g-150mAh / g.
[0044] The positive electrode active material exhibits a high discharge specific capacity at a 1C rate, indicating that it has good charge and discharge capabilities, which is beneficial for improving the battery's dynamic performance.
[0045] In any embodiment, the discharge capacity η of the positive electrode active material discharged to 3.2V accounts for ≥85%, where η is defined as follows: at room temperature, a coin cell containing the positive electrode active material is charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, followed by a constant current charge and discharge once at a constant current of 1C. In the 1C charge and discharge test, the capacity value extracted at a discharge voltage of 3.2V is recorded as C1, and the capacity value extracted at a discharge voltage of 2.0V is recorded as C2, where η = C1 / C2. The charging process includes constant voltage charging, with a constant voltage of 3.75V and a constant voltage cutoff current of 50μA.
[0046] The high discharge capacity ratio of the positive electrode active material used in the lithium-ion secondary battery of this application to 3.2V indicates that the positive electrode active material has good kinetic performance. At the same time, the high η value indicates that the lithium-ion secondary battery containing the positive electrode active material still has a high voltage when discharged to a low state of charge (SOC), which is beneficial for maintaining good power performance.
[0047] In any embodiment, the positive electrode film layer further includes a conductive agent, the mass content of which is 0.01%-1.5% based on the total mass of the positive electrode film layer.
[0048] Because the particles in this positive electrode film have formed a good stacking structure, the positive electrode active material particles are coated with a highly graphitized carbon layer on the surface and are in full contact with each other, resulting in good electronic conductivity. This reduces the amount of conductive agent used in the positive electrode film, which is beneficial to further increase the loading of the positive electrode active material and improve the energy density of the lithium-ion secondary battery.
[0049] In any embodiment, based on the total mass of the positive electrode film, the mass content of the positive electrode active material is 92%-99.5%, optionally 96.5%-99.5%.
[0050] When the mass content of the positive electrode active material and the mass content of the binder are within the above range, the loading of active material in the positive electrode film layer per unit volume can be effectively increased, while maintaining good internal adhesion, reducing the probability of powder shedding, expansion and cracking, and improving the energy density of the secondary battery while taking into account safety performance.
[0051] In any embodiment, the positive electrode film layer further includes a binder, wherein the binder has a mass content of 0.5%-3%.
[0052] In any embodiment, the one-sided density of the positive electrode film is 300 mg / 1540 mm². 2 -450mg / 1540mm 2 A cathode film with an areal density within the above range can help improve the energy density of lithium-ion secondary batteries.
[0053] In any embodiment, the positive electrode film layer of the lithium-ion secondary battery in its fully discharged state has a compaction density of 2.52 g / cm³. 3 -2.78g / cm 3 .
[0054] In any embodiment, the positive electrode film layer of the lithium-ion secondary battery in a fully discharged state has a compaction density of 2.55 g / cm³. 3 -2.75g / cm 3 .
[0055] A compaction density of the positive electrode film within the above-mentioned range is beneficial to improving the energy density of lithium-ion secondary batteries.
[0056] In any embodiment, the positive electrode film layer of the lithium-ion secondary battery in its fully discharged state has a compaction density of 2.52 g / cm³. 3 -2.78g / cm 3 In the cross-section along the thickness direction of the electrode sheet, the porosity of the positive electrode film is 10%-22%.
[0057] In any embodiment, the positive electrode film layer of the lithium-ion secondary battery in a fully discharged state has a compaction density of 2.55 g / cm³. 3 -2.75g / cm 3 In the cross-section along the thickness direction of the electrode sheet, the porosity of the positive electrode film is 10%-20%.
[0058] The lower the porosity in the cross-section of the positive electrode film, the better the gradation of large, medium and small particles in the positive electrode film and the higher the compaction density. On the other hand, under the same gradation and roller pressure, if the porosity is low, it means that the particles are more likely to slide against each other, thereby reducing the risk of overpressure and stress concentration in the film, further reducing the probability of the positive electrode film demolding during long cycles, which is beneficial to improving the long cycle performance of the battery.
[0059] In any embodiment, the positive electrode sheet includes a base coating layer disposed between the positive electrode film layer and the positive electrode current collector; the base coating layer satisfies at least one of the following conditions: (1) the base coating layer includes carbon-based particles, and the distribution density of carbon-based particles with a particle size greater than 100 nm in the base coating layer is ≤10 pcs / 10 μm; (2) the compaction density of the positive electrode sheet in the fully loaded state is greater than or equal to 2.4 g / cm³. 3 The thickness of the base coating on one side is 1μm-4μm; (3) the compaction density of the positive electrode sheet in the fully loaded state is greater than or equal to 2.5g / cm³. 3 The thickness of the base coating layer on one side is 2μm-4μm.
[0060] The undercoat layer helps improve the conductivity and adhesion between the positive electrode film and the current collector, reduces the detachment of the positive electrode film from the current collector during cycling, and improves the dynamic performance of the battery.
[0061] As the compaction density of the electrode increases, the compressive effect of large lithium phosphate particles (e.g., particles larger than 1 μm) on the undercoat becomes increasingly significant. Therefore, stress concentration easily occurs at large particle sites, and these particles can even penetrate the undercoat and damage the current collector. Increasing the thickness of the undercoat helps to mitigate stress concentration in the electrode, further improving the electrode's ultimate compaction density.
[0062] A second aspect of this application provides a battery device including the lithium-ion secondary battery of the first aspect of this application.
[0063] A third aspect of this application provides an electrical device, including at least one of the lithium-ion secondary battery of the first aspect of this application and the battery device of the second aspect of this application.
[0064] A fourth aspect of this application provides a method for preparing a positive electrode active material, the method comprising: obtaining a first positive electrode active material component and a second positive electrode active material component; mixing the first positive electrode active material component and the second positive electrode active material component, adding a carbon source to obtain a mixed positive electrode active material component; subjecting the mixed positive electrode active material component to a third sintering to obtain a sintered product, and crushing the sintered product to obtain a positive electrode active material; wherein, the first positive electrode active material component has a D V50The D of the second positive electrode active material component is 0.35μm-0.45μm. V50 The thickness is 0.25μm-0.35μm, and the mass ratio of the first positive electrode active material component to the second positive electrode active material component is (60:40)-(70:30).
[0065] By controlling the mass ratio of the first positive electrode active material component and the second positive electrode active material component, the area ratio and distribution of particles of different sizes can be precisely controlled to obtain the desired packing structure.
[0066] In any embodiment, the preparation method of the first positive electrode active material includes: obtaining a first mixed raw material comprising a first carbon source, a first lithium source, a first iron source, a first phosphorus source and a solvent; grinding the first mixed raw material to obtain a first mixed slurry; drying the first mixed slurry to obtain a first precursor powder; and subjecting the first precursor powder to a first sintering to obtain the first positive electrode active material; wherein the atomic molar ratio of iron to phosphorus in the first mixed raw material is 0.95-1; and the sintering temperature is 765℃-795℃.
[0067] In any embodiment, the preparation method of the second positive electrode active material includes: obtaining a second mixed raw material comprising a second carbon source, a second lithium source, a second iron source, a second phosphorus source and a solvent; grinding the second mixed raw material to obtain a second mixed slurry; drying the second mixed slurry to obtain a second precursor powder; and subjecting the second precursor powder to a second sintering to obtain the second positive electrode active material; wherein the sintering temperature is 705℃-735℃.
[0068] By controlling the first and second sintering processes, the final particle size and distribution of the first and second positive electrode active materials can be affected. This effectively shortens the sintering time in the high-temperature range of the third sintering process involving the mixed positive electrode active materials, preventing abnormal particle growth and grain coarsening caused by excessively long sintering times. Adjusting the particle size of the two grinding processes during the second sintering process controls the particle activity, resulting in a larger area of the positive electrode active material that meets the R2 particle size requirement. This improves the electrode compaction density, enhances the energy density of the battery cell, and simultaneously improves the cycle performance of the battery cell.
[0069] The fifth aspect of this application provides a method for preparing a positive electrode sheet, the method comprising sequentially adding a binder, a conductive agent, and a positive active material prepared by the method of the fourth aspect of this application, dry mixing them, adding a solvent, stirring, adjusting the viscosity, and obtaining a slurry; transferring the slurry to at least one side of a positive current collector, drying, and hot pressing to obtain a positive electrode film layer.
[0070] In any embodiment, the viscosity of the shipped slurry is 8000 Pa·s-12000 Pa·s.
[0071] In any embodiment, the hot pressing includes at least three hot roller pressings, with the hot roller pressure increasing sequentially to 20-50 tons, 50-70 tons, and 70-90 tons; the hot roller temperature is 40℃-80℃, and the positive electrode sheet is heated to 40℃-50℃ before the first hot roller compaction.
[0072] The positive electrode active material prepared by the above-mentioned shipping viscosity, hot pressing process and preparation method in the fourth aspect of this application is beneficial to further reduce the cross-sectional porosity of the positive electrode film, increase the ultimate compaction density of the electrode sheet and improve the energy density of the battery.
[0073] The above description is merely an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, specific embodiments of this application are given below. Attached Figure Description
[0074] Figure 1 This is a scanning electron microscope image of a cross-section of the positive electrode film layer along the electrode thickness direction according to an embodiment of this application;
[0075] Figure 2 This is a schematic diagram of a lithium-ion secondary battery according to one embodiment of this application;
[0076] Figure 3 This is an exploded view of a lithium-ion secondary battery according to one embodiment of this application;
[0077] Figure 4 This is a schematic diagram of a battery module according to one embodiment of this application;
[0078] Figure 5 This is a schematic diagram of a battery pack according to one embodiment of this application;
[0079] Figure 6 yes Figure 5 An exploded view of the battery pack shown.
[0080] Figure 7 This is a schematic diagram of a power supply device for a lithium-ion secondary battery according to an embodiment of this application.
[0081] Figure 8 This is a porosity test diagram of a cross-section along the thickness direction of the positive electrode film layer according to an embodiment of this application.
[0082] Explanation of reference numerals in the attached figures:
[0083] 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Secondary battery; 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation
[0084] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the lithium-ion secondary battery, battery device, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0085] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0086] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.
[0087] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.
[0088] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0089] In this application, the terms "multiple" or "various" refer to two or more kinds of things.
[0090] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.
[0091] Unless otherwise stated, the values of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in the embodiments of this application. Unless otherwise stated, the test temperature for each parameter is 25°C.
[0092] The battery mentioned in the embodiments of this application can be a single physical module comprising one or more lithium-ion secondary batteries to provide higher voltage and capacity. For example, the battery mentioned in this application may include lithium-ion secondary batteries, battery cells, battery modules, or battery packs.
[0093] A lithium-ion secondary battery is the smallest unit that makes up a battery, and it can independently perform the functions of charging and discharging. Lithium-ion secondary batteries can be cylindrical, cuboid, or other shapes, and the embodiments of this application are not limited in this respect. Figure 2 This is an example of a cuboid-structured lithium-ion secondary battery.
[0094] Lithium-ion secondary batteries consist of electrode components and electrolyte.
[0095] Lithium-ion secondary batteries may also include an outer packaging that encapsulates the electrode components and electrolyte. The outer packaging can be a rigid shell, such as a hard plastic shell, aluminum shell, or steel shell. It can also be a flexible package, such as a pouch. The material of the flexible package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0096] In some implementations, such as Figure 3As shown, the outer packaging may include a housing 51 and a top cover assembly 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates enclosing a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the top cover assembly 53 is used to cover the opening to close the receiving cavity. Electrode assemblies 52 are encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the lithium-ion secondary battery 5 may be one or more, and can be adjusted according to requirements.
[0097] Electrode assemblies typically include positive and negative electrodes. The negative electrode is the electrode that absorbs or lithiates lithium ions during charging and releases or delithiates lithium during discharging. The positive electrode is the electrode that absorbs or delithiates lithium ions during charging and absorbs or lithiates lithium during discharging.
[0098] When multiple lithium-ion secondary batteries are present, they are connected in series, parallel, or mixed via a busbar. In some embodiments, the battery can be a battery module; when multiple lithium-ion secondary batteries are present, they are arranged and fixed to form a battery module. In some embodiments, the battery can be a battery pack, which includes a housing and lithium-ion secondary batteries, with the lithium-ion secondary batteries or battery modules housed within the housing. In some embodiments, the housing can be part of the vehicle's chassis structure. For example, a portion of the housing can be at least part of the vehicle's floor, or a portion of the housing can be at least part of the vehicle's crossbeams and longitudinal beams.
[0099] In some implementations, the battery can be an energy storage device. Energy storage devices include energy storage containers, energy storage cabinets, etc.
[0100] In some implementations, lithium-ion secondary batteries can be assembled into battery modules, and the number of lithium-ion secondary batteries contained in a battery module can be multiple, the specific number of which can be adjusted according to the application and capacity of the battery module. Figure 4 This is a schematic diagram of battery module 4 as an example. Figure 4 As shown, in battery module 4, multiple lithium-ion secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple lithium-ion secondary batteries 5 can be fixed in place using fasteners.
[0101] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of lithium-ion secondary batteries 5 are received.
[0102] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0103] Figure 5 and Figure 6 This is a schematic diagram of battery pack 1 as an example. Figure 5 and Figure 6 As shown, the battery pack 1 may include a housing and multiple battery modules 4 disposed within the housing. The housing includes an upper housing 2 and a lower housing 3. The upper housing 2 covers the lower housing 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the housing.
[0104] Lithium-containing transition metal phosphate materials have been widely used in lithium-ion batteries due to their stable structure, good safety and long cycle life; however, they have problems such as low electronic conductivity and low stacking efficiency, which makes it difficult to further increase the loading of lithium-containing transition metal phosphates per unit volume of battery, thus failing to meet the needs of high energy density batteries.
[0105] To further improve battery energy density and electrode compaction density, the industry typically optimizes particle size distribution by combining particles of different sizes to enhance the packing density and compaction performance of the material. Existing gradation theory is based on a gap-filling theory, where large particles are tightly packed and small particles fill the gaps between them. However, small particles tend to agglomerate during the slurry mixing process, failing to fill the pores between large particles as intended; similarly, large particles are not perfectly round, making it difficult to achieve the theoretically close packing. Furthermore, the difference in specific surface area between particles of different sizes leads to varying degrees of electrochemical reaction with the electrolyte, resulting in differences in local lithium-ion concentration and diffusion rates, affecting ion transport stability. Simultaneously, during charge and discharge, the active material undergoes volume expansion and contraction; particles of different sizes may exhibit inconsistent expansion, potentially causing uneven mechanical stress between particles, thus affecting electrode structural stability and degrading battery performance after multiple cycles. Therefore, obtaining a battery that simultaneously achieves high energy density and good cycle performance is a pressing technical problem that needs to be solved in this field.
[0106] The first aspect of this application provides a lithium-ion secondary battery, comprising a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive current collector and a positive electrode film disposed on at least one side of the positive current collector. The positive electrode film includes a positive active material, comprising lithium transition metal phosphate particles with at least a carbon coating on their surface. Based on the total area of particles in a cross-section along the thickness direction of the positive electrode film, the area percentage of particles with a particle size R1 satisfying 1.5 μm ≤ R1 < 5 μm is 10.0%-20.0%, the area percentage of particles with a particle size R2 satisfying 50 nm ≤ R2 < 200 nm is 5.0%-12.0%, and the area percentage of particles with a particle size R3 satisfying 200 nm ≤ R3 < 1.5 μm is 73.0%-80.0%. The particle size distribution (D) of particles with a particle size R3 is... A90 -D A10 ) / D A50 The range is 1.40-1.683.
[0107] In existing technologies, the electrode compaction density and battery energy density are often improved by increasing the proportion of larger and smaller particles in the positive electrode film layer. However, studies show that when the area ratio of particles with a particle size R1 satisfying 1.5μm≤R1<5μm exceeds 20%, although this is beneficial for improving the high compaction density of the positive electrode, it will increase the diffusion path of lithium ions in the particles, increase battery impedance, and deteriorate the battery's kinetic performance. When the area ratio of particles with a particle size R1 satisfying 1.5μm≤R1<5μm is less than 10%, the proportion of large particles that form the framework is insufficient, making it difficult to further improve the compaction density of the positive electrode and the energy density of the battery. Furthermore, the structural stability of the positive electrode is also significantly reduced, which also affects the battery's cycle performance. When the area ratio of particles with a particle size R2 satisfying 50nm≤R2<200nm is less than 5%, the proportion of small particles filling the gaps is insufficient, resulting in high porosity inside the positive electrode film, which restricts the battery's energy density. When the area ratio of particles with a particle size R2 satisfying 50nm≤R2<200nm is greater than 12%, the specific surface area of the particles is large, making them prone to side reactions with the electrolyte. This will reduce the battery's cycle performance. During the research process, the applicant discovered that the area of particles with a particle size R3 satisfying 200nm≤R3<1.5μm plays an important role in optimizing the packing structure of the positive electrode film. When the area of particles with a particle size R3 satisfying 200nm≤R3<1.5μm accounts for less than 73%, the proportion of R1 and R2 particles is large, and the large difference in particle size between R1 and R2 particles leads to inconsistent degrees of electrochemical reaction, resulting in increased battery polarization and deterioration of cycle performance. When the area of particles with a particle size R3 satisfying 200nm≤R3<1.5μm accounts for more than 80%, the proportion of R1 and R2 particles is too small, which increases the porosity of the film and is not conducive to forming a tight packing in the film and reducing electrode compaction.
[0108] In this embodiment, the positive electrode sheet achieves the following by controlling the area ratio of particles with diameter R1 satisfying 1.5μm≤R1<5μm to be 10.0%-20.0%, particles with diameter R2 satisfying 50nm≤R2<200nm to be 5.0%-12.0%, and particles with diameter R3 satisfying 200nm≤R3<1.5μm to be 73.0%-80.0%. The particle size distribution (D) of particles satisfying diameter R3 is also controlled. A90 -D A10 ) / D A50 A particle size distribution of 1.40-1.683 helps improve the uniformity of lithium-ion diffusion rates and reduces the overall specific surface area difference of particles within the film, allowing for more uniform contact with lithium-ions in the electrolyte, thereby improving the battery's ion conductivity and stability. Simultaneously, a certain particle size gradient is formed within the R3 particles. Through the synergistic effect of particles of different sizes, the interlocking effect between particles is optimized, effectively reducing the overall porosity. The entire packing system achieves a more compact arrangement, thus significantly improving the compaction density. In this gradation, particles of different sizes also have complementary properties in stress distribution and inter-particle interactions, enabling the material to increase overall stability under external pressure through mechanical interlocking, achieving a balance between energy density and cycle performance.
[0109] Lithium-containing transition metal phosphates refer to phosphate materials containing lithium and transition metal elements, and can be detected by any method known in the art. For example, they can be detected by combining X-ray diffraction (XRD) with energy dispersive spectroscopy (EDS).
[0110] The carbon coating layer disposed on at least a portion of the surface of lithium-containing transition metal phosphates can be detected by any method known in the art. As an example, the carbon coating layer disposed on at least a portion of the surface of lithium-containing transition metal phosphates can be observed by characterizing lithium-containing transition metal phosphates using a combination of transmission electron microscopy and energy dispersive spectroscopy.
[0111] In this application, the term "particle" refers to a particle in the positive electrode film layer that has a recognizable complete boundary in the field of view at a certain magnification, such as 10,000x. Defects and scratches may exist inside the particle, but a complete boundary sufficient to divide the particle cannot be identified inside the particle.
[0112] The particle identification method is as follows: The positive electrode film is cut along the thickness direction of the electrode sheet using an argon ion beam. After exposing the cut surface, a scanning electron microscope (SEM) is used to observe the cut surface along the thickness direction of the positive electrode film. Images are acquired in secondary electron mode at non-edge positions in the cut surface of the positive electrode film using a field emission scanning electron microscope (after observing the electrode edge under the SEM, the field of view is adjusted to the center of the sample). Electron micrographs are taken at 10kx magnification, and the particles in the electron micrographs are analyzed using ImageJ software (1.46r, Win64 version). The specific usage of ImageJ software is as follows: Load the SEM image to be analyzed; use the Cellpose plugin software to identify particles, and perform manual corrections; use ImageJ to read and analyze data. The specific method for identifying particles using the Cellpose plugin software is as follows: Set the segmentation diameter parameter (diameter in the Segmentation module) to 15 pixels, click "run cyto3" to identify particles; manually mark particles in the image that were not identified by the software, were not fully identified by the software, or had identification errors. Among them, particles in the image that were not recognized by the software, were not fully recognized by the software, or were recognized with errors mainly include the following types: 1. Due to the particle being too large or having scratches on the particle surface, the particle cannot be recognized or cannot be fully recognized; 2. During the argon ion beam cutting process, scratches will be generated on the particle surface. The software may misjudge the scratches as particle boundaries during the recognition process, thus causing recognition errors; 3. Due to the particle being too small, it was not successfully recognized; 4. The particle is located at the edge of the electron microscope field of view, and the interior of the particle is penetrated by the edge, so the morphology cannot be fully displayed. The part is recognized instead of the whole, resulting in recognition errors. For the unidentified or misidentified particles mentioned above, manual calibration is performed as follows: Particles located at the edges of the scanning electron microscope that are not fully displayed are deleted; It is determined whether other unidentified or misidentified particles have internal cracks or scratches. If no cracks or scratches are found, the particle is considered a single particle, and its boundary is manually marked based on observation; If cracks or scratches are found within the particle, it is determined whether the cracks or scratches penetrate the particle. If not, it is considered a single particle and manually marked; If the cracks or scratches penetrate the particle, it is determined whether the cracks or scratches are linear or irregular; If the cracks or scratches are irregular, they are considered the boundary between particles, and particles are divided along this boundary; If the cracks or scratches are linear, contrast is compared; If the contrast is not obvious and there is no crack-like appearance, it is considered a scratch and marked as a single particle; If the contrast is strong and there is a crack-like appearance, it is considered the boundary between particles and marked as two particles. After manual marking, irrelevant information from the automatic image processing is deleted, thus completing the particle identification and marking in the image.
[0113] The specific method for calculating the area ratio of particles in the cross-section along the thickness direction of the positive electrode film is as follows. After particle identification and labeling, the image is imported into ImageJ software for analysis. The scale is set based on the scanning electron microscope image. The particle size and area in the cross-section along the thickness direction of the positive electrode film are analyzed using the "Feret Diameter," "Area," "Round," and "Solidity" analysis functions. According to the software manual (ImageJ User Guide IJ1.46r), the obtained "Feret" parameter represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size; and the obtained "Area" parameter represents the pixel area of the particle. Since particles with a diameter less than 50nm have a large error in the statistical process and are difficult to accurately identify, and the particle size of conductive agents is generally less than 50nm, which will introduce a large error into the statistical results, particles with a diameter less than 50nm are not counted in the particle size statistics process of this application, and the particle statistics data corresponding to AR, Round, or Solidity values displayed as "NaN" are deleted. Following the above method, to ensure a statistically significant sample size, at least 10 scanning electron microscope (SEM) images were acquired for each electrode, and the particle size and area of at least 5000 particles were statistically analyzed. The total area of particles with a diameter R1 satisfying 1.5μm ≤ R1 < 5μm, calculated using the particle's "Area," was divided by the total area of all identified particles. This area was used as the percentage of particles with a diameter R1 satisfying 1.5μm ≤ R1 < 5μm in a cross-section along the electrode thickness direction. Similarly, the total area of particles with a diameter R2 satisfying 50nm ≤ R2 < 200nm, calculated using the particle's "Area," was also used as the percentage of particles with a diameter R2 satisfying 50nm ≤ R2 < 200nm in a cross-section along the electrode thickness direction. The total area of particles with a diameter R3 of 200nm ≤ R3 < 1.5μm is calculated by dividing the sum of the areas of particles with a diameter R3 of 200nm ≤ R3 < 1.5μm by ...
[0114] In some embodiments, based on the total area of particles in the cross-section of the positive electrode film along the electrode thickness direction, the area percentage of particles with a particle size R1 satisfying 1.5μm≤R1<5μm can be selected as 10%, 10.69%, 11%, 12%, 13%, 13.34%, 14%, 14.23%, 14.64%, 15%, 15.01%, 15.45%, 15.98%, 16%, 16.23%, 17%, 17.55%, 18%, 18.01%, 19%, 19.21%, 20%, or any value range between the two.
[0115] In some embodiments, based on the total area of particles in the cross-section of the positive electrode film along the thickness direction of the electrode sheet, the area percentage of particles with a particle size R2 satisfying 50nm≤R2<200nm can be selected as 5%, 5.12%, 6%, 6.43%, 7%, 7.28%, 7.75%, 8%, 8.01%, 8.33%, 8.78%, 8.87%, 9%, 9.36%, 9.64%, 10%, 11%, 11.51%, 12%, or any value range between the two.
[0116] In some embodiments, based on the total area of particles in the cross-section of the positive electrode film along the thickness direction of the electrode sheet, the area percentage of particles with a particle size R3 satisfying 200nm≤R3<1.5μm can be selected as 73%, 73.04%, 73.12%, 73.85%, 74%, 74.44%, 75%, 75.35%, 76%, 76.22%, 77%, 77.59%, 77.88%, 78%, 78.49%, 78.65%, 79%, 79.95%, 80%, or any value range between the two.
[0117] In some implementations, the particle size distribution (D) of particles satisfying R3 is... A90 -D A10 ) / D A50 The range is 1.40-1.683.
[0118] Particle size distribution (D) of particles whose size satisfies R3 A90 -D A10 ) / D A50 The calculation method is as follows. Following the method described above in this application, particles in the cross-section of the positive electrode film are identified. The morphology of the particles in the cross-section along the thickness direction of the positive electrode film is analyzed using the "Feret" and "Area" analysis functions in ImageJ. To ensure a statistically significant sample size, at least 10 scanning electron microscope images are acquired for each electrode, and the particle size of at least 5000 particles is counted. The particle sizes of the at least 5000 particles are arranged in ascending order. The cumulative area distribution curve of the particles in the positive electrode film is obtained by plotting the particle size on the horizontal axis and the cumulative area percentage calculated from the "Area" of the particles on the vertical axis. A90 D A50 D A10 These represent the particle size values corresponding to the cumulative quantity percentages of the vertical axis in the area cumulative distribution curve at 90%, 50%, and 10%, respectively.
[0119] In some implementations, the particle size distribution (D) of particles satisfying R3 is... A90 -D A10 ) / D A50The value can be selected from 1.40, 1.402, 1.41, 1.42, 1.43, 1.44, 1.45, 1.46, 1.47, 1.48, 1.484, 1.49, 1.491, 1.50, 1.505, 1.511, 1.538, 1.563, 1.593, 1.51, 1.52, 1.53, 1.54, 1.55, 1.56, 1.57, 1.58, 1.59, 1.60, 1.603, 1.61, 1.62, 1.63, 1.64, 1.65, 1.66, 1.67, 1.68, 1.683, or any range between two values.
[0120] The cross-sectional morphology of the positive electrode film along the thickness direction of the electrode sheet is shown in the figure. Figure 1 As shown, the state of the positive electrode active material differs from that observed by Malvern laser scattering and also from that observed directly by scanning electron microscopy. Under roller pressure, the particles in the positive electrode film exhibit a well-dispersed state, making observation of the positive electrode film beneficial for effectively characterizing the particle size and area within it.
[0121] During the compaction process, the positive electrode film is compacted in the thickness direction. The cross-section of the positive electrode film along the thickness direction is more reflective of the actual compaction of the particles inside the film in a spatial scale than the surface of the positive electrode film.
[0122] In some embodiments, the area ratio of particles with a particle size R3 satisfying 200nm≤R3<1.5μm is 74.0%-78.0%.
[0123] In the positive electrode film, particles with a diameter R3 satisfying 200nm ≤ R3 < 1.5μm are easier to fill gaps than particles with a diameter greater than or equal to 1.5μm, achieving a higher packing density. Compared to particles with a diameter less than 200nm, their larger volume provides better support for the large particle packing framework, reducing the possibility of deformation or stress concentration due to expansion or external forces, thus improving structural stability. Therefore, a particle area ratio of 200nm or greater and less than 1.5μm within this range can further improve the compaction density and structural strength of the entire particle system, thereby increasing the battery's energy density and cycle performance.
[0124] In some embodiments, the area percentage of particles with a particle size R2 satisfying 50nm≤R2<200nm is 6.0%-10.0%.
[0125] Since the area of a single particle with a particle size R2 satisfying 50nm≤R2<200nm is small, it can effectively fill the gaps between particles, thereby improving the stacking structure and density of the electrode; the overall area ratio of particles within this particle size range is small, which at the same time reduces the probability of side reactions and improves the cycle performance of the battery.
[0126] In some embodiments, the area ratio of particles with a particle size R1 satisfying 1.5μm≤R1<5μm is 13.0%-18.0%.
[0127] In the cross-section of the positive electrode film along the thickness direction of the electrode sheet, particles with a particle size R1 satisfying 1.5μm≤R1<5μm can occupy a certain space in the stacking and provide a structural framework due to their larger particle size and stronger geometric stability. This optimizes the arrangement between particles, further improves the compaction density of the electrode sheet, and improves the energy density of the battery.
[0128] In some embodiments, the median L of the spheroidal density in the cumulative distribution curve of the particle spheroidal density of the particles obtained from a cross-section of the positive electrode film along the electrode thickness direction is... A50 The value is 0.70-0.85, and can be selected as 0.70-0.76.
[0129] In the cross-section of the positive electrode film along the electrode thickness direction, the median sphericity L 50 The specific testing method is as follows: Particles in the cross-section of the positive electrode film layer are identified using the method described above in this application. The morphology and area of the particles in the cross-section along the electrode thickness direction of the positive electrode film layer are analyzed using the "Shape Description" and "Area" analysis functions in ImageJ. According to the software manual (ImageJ User Guide IJ1.46r), the "Area" parameter obtained from the analysis represents the pixel area of the particle, and the "Round" parameter represents the ratio of the pixel area of the particle to the area of a circle with the fitted major axis as its diameter. The closer the particle is to a sphere, the closer the ratio of the pixel area to the area of the circle with the fitted major axis as its diameter is to 1. Therefore, the "Round" parameter of the analyzed particles characterizes the sphericity of the particles. The sphericity of at least 5000 particles is arranged in ascending order, and the cumulative distribution curve of the sphericity area of the particles in the positive electrode film layer is obtained with sphericity as the horizontal axis and the cumulative area ratio as the vertical axis. L A50 This is the L-value of sphericity when the cumulative area under the vertical axis of the cumulative distribution curve of L-values accounts for 50%.
[0130] In some embodiments, the median L of the spheroidal density is obtained from the cumulative distribution curve of the spheroidal area of the particles obtained by slicing the positive electrode film along the thickness direction of the electrode sheet. A50The value can be selected from 0.70, 0.709, 0.71, 0.719, 0.72, 0.725, 0.726, 0.73, 0.737, 0.74, 0.75, 0.751, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, or any value range between the two.
[0131] Those skilled in the art can control the sphericity of particles using any known process. For example, the sphericity of particles can be adjusted through processes such as grinding, polishing, chemical etching, mechanical stirring, extrusion, coating, granulation, and adding surfactants, as well as by adjusting the parameters of each process.
[0132] Median L of sphericity A50 Within the aforementioned range, the particles are approximately spherical, which helps them maintain good slidability during stacking, making it easier to fill the gaps between particles. This further improves the compaction density of the electrode and increases the energy density of the battery.
[0133] In some embodiments, the median L of the spheroidality is obtained from the cumulative distribution curve of the spheroidality area of particles with a particle size R1 satisfying 1.5 μm ≤ R1 < 5 μm along the cross-section of the positive electrode film along the electrode thickness direction. R1A50 It is 0.70-0.76.
[0134] The sphericity area cumulative distribution curve of particles with a particle size R1 satisfying 1.5μm≤R1<5μm obtained from the cross-section of the positive electrode film along the electrode thickness direction is determined as follows: Particles in the cross-section of the positive electrode film are identified using the method described above in this application. While using the "Feret" function in ImageJ to identify the particle size in the positive electrode film, the "Shape Description" and "Area" analysis functions are used to analyze the morphology and area of the particles in the cross-section along the electrode thickness direction. According to the software manual (ImageJ User Guide IJ 1.46r), the analyzed "Area" parameter represents the pixel area of the particle, and the "Round" parameter represents the ratio of the pixel area of the particle to the area of a circle with the fitted major axis as its diameter. The closer the particle is to a sphere, the closer the ratio of the pixel area to the area of the circle with the fitted major axis as its diameter is to 1. Therefore, the "Round" parameter of the analyzed particles characterizes the sphericity of the particles.
[0135] The sphericity of particles with a diameter R1 satisfying 1.5 μm ≤ R1 < 5 μm is arranged in ascending order. A cumulative distribution curve of the sphericity area of the particles in the positive electrode film is obtained by plotting sphericity on the horizontal axis and the cumulative area percentage calculated from the particle's "Area" on the vertical axis. The median sphericity refers to the sphericity corresponding to a cumulative area percentage of 50% on the vertical axis of the cumulative distribution curve. The median sphericity of particles with a diameter R2 satisfying 50 nm ≤ R2 < 200 nm and the median sphericity of particles with a diameter R3 satisfying 200 nm ≤ R3 < 1.5 μm can be obtained similarly.
[0136] In some embodiments, the median of the spheroidity in the cumulative distribution curve of the spheroidity area of particles with a particle size R1 satisfying 1.5 μm ≤ R1 < 5 μm obtained from the cross-section of the positive electrode film along the electrode thickness direction can be selected as 0.70, 0.71, 0.715, 0.718, 0.72, 0.722, 0.728, 0.73, 0.734, 0.737, 0.74, 0.745, 0.75, 0.76 or any value range between the two.
[0137] The median sphericity of particles with a particle size R1 satisfying 1.5μm≤R1<5μm is within the above range, which effectively improves the problem of poor sphericity of large particles, reduces particle bridging caused by the irregular shape of large particles, and reduces the void content in the electrode sheet; while retaining a certain degree of irregularity, it helps to form a structural network with a certain strength between particles, which can withstand greater rolling pressure and internal and external stress, thus improving the compaction density of the electrode sheet and the energy density of the battery.
[0138] In some embodiments, the median L of the sphericity is obtained from the cumulative distribution curve of the sphericity area of particles with a particle size R2 satisfying 50nm ≤ R2 < 200nm along the cross-section of the positive electrode film along the electrode thickness direction. R2A50 It is 0.73-0.80.
[0139] In some embodiments, the median of the spheroidity in the cumulative distribution curve of the spheroidity area of particles with a particle size R2 satisfying 50nm≤R2<200nm obtained from the cross-section of the positive electrode film along the electrode thickness direction can be selected from 0.73, 0.732, 0.74, 0.749, 0.75, 0.755, 0.757, 0.758, 0.76, 0.761, 0.77, 0.778, 0.779, 0.78, 0.789, 0.79, 0.793, 0.80 or any value range between the two.
[0140] The median sphericity of particles with a particle size R2 satisfying 50nm≤R2<200nm is within the above range. Small particles have high sphericity, and regularly shaped small particles are beneficial for filling the voids in the electrode sheet, further improving the compaction density of the electrode sheet and the energy density of the battery.
[0141] In some embodiments, the median L of the spheroidal density is obtained from the cumulative distribution curve of the spheroidal area of particles with a particle size R3 satisfying 200 nm ≤ R3 < 1.5 μm along the cross-section of the positive electrode film along the electrode thickness direction. R3A50 It is 0.71-0.77.
[0142] In some embodiments, the median of the spheroidity in the cumulative distribution curve of the spheroidity area of particles with a particle size R3 satisfying 200nm≤R3<1.5μm obtained from the cross-section of the positive electrode film along the electrode thickness direction can be selected as 0.71, 0.72, 0.724, 0.73, 0.733, 0.734, 0.74, 0.744, 0.745, 0.75, 0.751, 0.76, 0.761, 0.77 or any value range between the two.
[0143] The median sphericity of particles with a particle size R3 satisfying 200nm≤R3<1.5μm is within the above range. Particles with an R3 particle size having the largest area distribution ratio have better sphericity, which is conducive to uniform slip between particles, reduces the probability of local stress concentration, and further improves the compaction density of the electrode.
[0144] In some embodiments, the median R of the particle roughness is obtained from the cumulative distribution curve of the particle roughness area obtained by slicing the positive electrode film along the electrode thickness direction. A50 It is 0.92-0.96.
[0145] The median roughness R in the cross-section of the positive electrode film along the electrode thickness direction is... A50 The specific testing method is as follows: Particles in the cross-section of the positive electrode film layer were identified using the method described above in this application. The morphology of the particles in the cross-section along the thickness direction of the positive electrode film layer was analyzed using the "Shape Description" analysis function in ImageJ. According to the software manual (ImageJ User Guide IJ1.46r), the "Solidity" parameter obtained from the analysis represents the ratio of the pixel area to the convex area of the particle. Therefore, the "Solidity" parameter of the analyzed particles is used to characterize the roughness of the particles. By definition, the closer the roughness is to 1, the smoother the particle. The roughness of at least 5000 particles was arranged in ascending order, and the cumulative area distribution curve of the particles in the positive electrode film layer was obtained with roughness as the horizontal axis and cumulative area percentage as the vertical axis. A50This is the roughness R value corresponding to the cumulative area ratio of the vertical axis in the cumulative distribution curve of roughness R value being 50%.
[0146] In some embodiments, the median R of the particle roughness is obtained from the cumulative distribution curve of the particle roughness area obtained by slicing the positive electrode film along the electrode thickness direction. A50 The value can be selected as 0.92, 0.93, 0.94, 0.95, 0.96 or any range between two of them.
[0147] Those skilled in the art can control the roughness of particles using any known process. For example, particle roughness can be adjusted through processes such as grinding, polishing, abrasion, milligram energy processing, electroplating, and calendering, as well as by adjusting the parameters of each process.
[0148] Median roughness R A50 Within the aforementioned range, the particle surface is relatively smooth, and the friction between particles is relatively small. Under the action of external force, it is easy to slip, which can further improve the compaction density of the electrode and increase the energy density of the battery.
[0149] In some embodiments, the median C of the graphitization degree C in the cumulative distribution curve of the positive electrode film obtained in the laser microscopy confocal Raman spectroscopy instrument scanning mode is... 50 The value is 0.98-1.20, and can be selected as 1.02-1.10, where the graphitization degree C value is I. G / I D I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of peak G at I D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.
[0150] In this application, the graphitization degree C value of the positive electrode film can be obtained by surface scanning mode of a laser confocal Raman spectrometer. As an example, specifically, a laser confocal Raman spectrometer (high-precision Renishaw laser confocal Raman spectrometer) is used, with an excitation wavelength of 532 nm. An appropriate amount of the positive electrode film is taken and surface scanned on its surface or along the thickness direction of the electrode. The scanning area is 45 μm × 45 μm, divided into 10 × 10 grids, with grid vertices as test points, a step size of 5 μm, and a total of 100 scan points. Thus, the C values at different sites and the cumulative distribution curve of the C values in the surface scan area are obtained.
[0151] The degree of graphitization C of the positive electrode film was obtained by the ratio of the peak intensities of the G-band and D-band in the Raman spectrum. The position of the G-band peak was 1585±100 cm⁻¹. -1Its characterization of carbon sp 2 Hybrid structure; D peak position is 1350±50 cm⁻¹ -1 It characterizes a disordered structure, where disorder refers to the irregular arrangement of carbon atoms within the structure. In graphite crystals, carbon atoms in the same layer arrange themselves in an sp... 2 Hybridization forms covalent bonds, while interlayer bonding is facilitated by van der Waals forces, making it easy for carbon in the graphite structure to slip. Therefore, the C value can characterize the degree of graphitization of the cathode active material. It is understood that the degree of graphitization of the lithium phosphate-containing cathode active material in this application mainly comes from its surface carbon coating layer.
[0152] The cumulative distribution curve of graphitization degree C value refers to the curve obtained by arranging at least 100 C values in ascending order, with graphitization degree as the horizontal axis and the cumulative percentage as the vertical axis. 50 This represents the C value corresponding to a cumulative percentage of 50% on the vertical axis of the cumulative distribution curve of graphitization degree C. The median C value of graphitization degree. 50 Compared to point values, it can reflect the overall graphitization degree of particles in the positive electrode film, i.e., the degree of slippage; compared to the mean value, it can reduce the influence of extreme values during the test and improve the confidence of the test results.
[0153] In some embodiments, the median C of the graphitization degree C in the cumulative distribution curve of the positive electrode film obtained in the laser microscopy confocal Raman spectroscopy instrument scanning mode is... 50 The value can be selected from 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, or any value range between the two.
[0154] The graphitization degree of the particles in the positive electrode film is within the above range, indicating that the proportion of graphitic carbon in the positive electrode film is high. The particles can easily slip by means of the highly graphitized carbon structure in the coating material. Combined with the high sphericity of the particles, it is more conducive to the slippage between particles, thereby improving the compaction density of the electrode sheet.
[0155] In some embodiments, the median B of the coating value B in the cumulative distribution curve of the positive electrode film obtained in laser microscopy confocal Raman spectroscopy instrument scanning mode is... 50 The value is 0.30-0.50, where the coating value B is I. P / I D , where I P This indicates that the Raman spectrum is at 948±100 cm⁻¹ -1 The intensity of the P peak at I DThis indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.
[0156] In this application, the coating value (B value) of the positive electrode film can be obtained by scanning with a laser confocal microscopy (LCM) spectrometer. Specifically, a high-precision Renishaw laser confocal microscopy (LCM) spectrometer is used, with an excitation wavelength of 532 nm. An appropriate amount of the positive electrode film is scanned on its surface or along a section of the electrode thickness. The scanning area is 45 μm × 45 μm, divided into 10 × 10 grids, with grid vertices as test points, a step size of 5 μm, and a total of 100 scan points. This yields the B values at different sites and the cumulative distribution curve of the B values in the scanned area.
[0157] The coating value B of the positive electrode film was obtained by the ratio of the peak intensities of the P-band and D-band in the Raman spectrum, with the P-band located at 948±100 cm⁻¹. -1 Its characterization of phosphate PO4 3- Structure; D peak position is 1350±100cm -1 Raman spectroscopy characterizes disordered structures, where disorder refers to the irregular arrangement of carbon atoms within the structure. As a surface analysis instrument, Raman spectroscopy reveals that the carbon structure peaks in the cathode film, under laser confocal Raman spectroscopy scanning mode, exhibit higher intensity compared to the phosphate structure peaks, which are more abundant in the bulk phase.
[0158] Those skilled in the art can control the coating value of active material particles using any known process. For example, adjusting the carbon source type, carbon source addition amount, sintering temperature, sintering time, sintering pressure, and sintering atmosphere can all achieve adjustments to the coating value of active material particles. The coating value (B-value) reflects the density of the carbon coating layer on the surface of lithium transition metal phosphate particles. The denser the carbon coating, the lower the relative intensity of the phosphate structure detected in the Raman spectrum, and the smaller the coating value (B-value) of the cathode film.
[0159] The cumulative distribution curve of the coverage value (B value) is a curve obtained by arranging at least 100 B values in ascending order, with the coverage value on the horizontal axis and the cumulative percentage on the vertical axis. 50 The B value is the B value corresponding to the cumulative number of values on the vertical axis of the cumulative distribution curve of the coverage value B value when the cumulative number accounts for 50%.
[0160] In some embodiments, the positive electrode film further includes a coating layer disposed on at least a portion of the surface of the lithium-containing transition metal phosphate particles, wherein the median B of the coating value B in the cumulative distribution curve of the coating value B obtained in the laser microscopy confocal Raman spectroscopy instrument scanning mode is... 50The value can be selected from 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.6, or any value range between the two.
[0161] To reduce the impact of extreme coating values caused by non-particle regions in the positive electrode film on the test results, the median coating value, B, was used. 50 To evaluate the density of carbon-coated materials on positive electrode active materials.
[0162] The median B of the coating value of the positive electrode film 50 Within the above range, it is indicated that the carbon coating material of the positive electrode active material is relatively dense and uniform, which is beneficial to improving the slippage of the positive electrode film during the rolling process, and further improving the compaction density of the electrode sheet and the energy density of the battery.
[0163] In some embodiments, the carbon content is 0.8%-1.8% by mass, and optionally 0.90%-1.5%, based on the total mass of the positive electrode active material.
[0164] Based on the total mass of the positive electrode active material, the mass content of carbon can be measured using methods and equipment known in the art. For example, it can be determined using a Dekai HCS infrared carbon and sulfur analyzer, referring to GB / T 21023-2006 "Determination of Total Carbon and Sulfur Content in Iron and Steel - Infrared Absorption Method After Combustion in a High-Frequency Induction Furnace".
[0165] In some embodiments, based on the total mass of the positive electrode active material, the mass content of carbon can be selected as 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, or any range between the two.
[0166] This positive electrode active material has a relatively low carbon coating content, which can further increase the loading of lithium transition metal phosphates in the positive electrode sheet and improve the energy density of lithium-ion secondary batteries.
[0167] In some embodiments, the lithium iron ion reverse defect concentration of the positive electrode active material is 0.001%-1.50%, optionally 0.01%-1.0%.
[0168] XRD data of the samples were collected using an X-ray diffractometer, and phase analysis was performed. The CIF file of the phase obtained from an open-source website was used as the initial crystal structure model, including the definition of unit cell parameters, atomic positions, and occupancy probabilities. In the initial crystal structure model, considering the possibility of Fe-Li antisites, the possible Li content at Fe sites and the possible Fe content at Li sites were set to an initial value of 0.1%. The collected XRD data were fitted and refined using FullProf Suite software, refining the parameters in the order of background parameters, peak intensity, unit cell parameters, and peak shape. When the fitted peak shape and the experimental peak shape were optimally matched, and Rwp was less than 10, the refined Li and Fe occupancy probabilities were obtained. The probability of iron occupying lithium sites was used as the concentration of lithium-iron antisite defects.
[0169] In some embodiments, the concentration of lithium iron ion reverse defects in the positive electrode active material can be selected as 0.001%, 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, or any value range between the two.
[0170] During preparation and cycling, lithium vacancies inevitably exist within the crystal structure of the positive electrode active material. These vacancies not only lead to the oxidation of ferrous ions to ferric ions but also induce partial migration of ferric ions to lithium sites, forming lithium-iron antisite defects. This blocks the one-dimensional diffusion channels of lithium ions, adversely affecting the solid-phase transport of lithium ions. The positive electrode active material in this application has low lithium-iron antisite defects, which is beneficial for the uniform transport of lithium ions in the solid phase and further improves the kinetic performance of the lithium-ion secondary battery.
[0171] In some embodiments, the lithium-containing transition metal phosphate particles comprise components having the following general formula:
[0172] Li m Fe x P y O j Q q ,
[0173] Wherein, Q includes one or more of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, with 0.8≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0≤q≤0.1.
[0174] In some implementations, m can be selected as 0.8, 0.85, 0.9, 0.95, 0.98, 1.00, 1.03, 1.05, 1.08, 1.10, 1.13, 1.15, or any value range between two of these; x can be selected as 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, or any value range between two of these. y can be 0.95, 0.96, 0.97, 0.98, 0.99, 1.00 or any value between two of these; j can be 3.5, 3.6, 3.7, 3.8, 3.9, 4 or any value between two of these; q can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or any value between two of these.
[0175] Selecting an appropriate modifying element Q can improve the ion diffusion pathway of the positive electrode active material, improve the lithium ion diffusion rate of the positive electrode active material, and improve the kinetic performance of the battery.
[0176] In some embodiments, the positive electrode active material includes one or more of lithium iron phosphate and its doped and modified materials, and coated and modified materials.
[0177] In some embodiments, the positive electrode active material includes titanium, and the mass content of titanium is 4000ppm-8000ppm based on the total mass of the positive electrode active material.
[0178] The types and contents of elements in positive electrode active materials can be tested using any method known in the art. As an example, inductively coupled plasma atomic emission spectrometry (ICP-AES) is used to test the titanium content, referring to Appendix C of GB / T 33822-2017.
[0179] Doping titanium in cathode active materials can induce lattice distortion, reduce Li-O bond energy, increase lithium-ion transport rate, and improve the kinetic performance of lithium-ion secondary batteries. However, in existing technologies, the doping content of titanium in lithium-containing transition metal phosphates often cannot exceed 3000 ppm, because excessive titanium is difficult to completely enter the bulk phase of lithium-containing transition metal phosphates and easily becomes a harmful impurity phase remaining on the surface, negatively impacting battery performance.
[0180] The positive electrode active material in this application embodiment has a high titanium content. Surprisingly, the high amount of titanium added did not form a harmful impurity phase that negatively affects the battery's energy density and kinetic performance. Although the reason is not yet clear, it is speculated that titanium, together with phosphate and other elements (e.g., lithium), forms a fast ion conductor, which instead improves the battery's kinetic performance.
[0181] In some embodiments, the tap density of the positive electrode active material is 1.00 g / cm³. 3 -1.70g / cm 3 1.20g / cm³ is an optional value. 3 -1.50g / cm 3 .
[0182] The tap density of powder can be obtained by any method known in the art. As an example, turn on the electronic balance, place a conical flask as a base on the balance, and then zero the balance. Place the tapped graduated cylinder on the conical flask, weigh it, and record the weight. Open the sample bag, use a clean sample spoon to stir the sample in the bag 3-5 times to mix it thoroughly, and then smoothly transfer the sample into the graduated cylinder. Wipe the powder adhering to the surface of the cylinder with lint-free paper, and then place it into the zeroed conical flask and weigh it. Seal the mouth of the graduated cylinder with sealing film, and place the tapped graduated cylinder into the matching instrument rubber ring to ensure proper vibration. The compacted density cylinder is tightly fitted to the rubber ring and kept perpendicular to the instrument surface. The vibration frequency is set to 250 times / min and the number of vibrations is 5000. The button is pressed and the cylinder vibrates for 20 minutes. Then, the compacted density cylinder is removed, and the surface of the cylinder is illuminated with a flashlight. The highest scale value V1 and the lowest scale value V2 are read visually, and the average value V is taken. The mass of the cylinder is obtained by subtracting the mass of the cylinder m0 from the mass of the sample m1. The mass of the powder m is obtained by using the density formula ρ=m / v.
[0183] In some embodiments, the tap density of the positive electrode active material powder can be selected as 1.00 g / cm³. 3 1.05g / cm 3 1.10 g / cm 3 1.15g / cm 3 1.20g / cm 3 1.25g / cm 3 1.30g / cm 3 1.35g / cm 3 1.40 g / cm 3 1.45g / cm 3 1.50g / cm 3 1.55g / cm 3 1.60g / cm 3 1.65g / cm 3 1.70g / cm 3 Or the range of values between any two.
[0184] In this embodiment, the positive electrode active material particles, through R3 particles with a certain distribution width, effectively reduce the overall porosity by optimizing the interlocking effect between particles, thus achieving a high tap density.
[0185] In some embodiments, the compacted density of the positive electrode active material at a pressure of 3T is 2.55 g / cm³. 3 -2.70g / cm 3 The option is 2.58g / cm³. 3 -2.68g / cm 3 .
[0186] In this application, the term "powder compaction density" refers to the density of a compacted compact with a certain density and strength, formed during the external force compression process. This density is measured in g / cm³, as the powder moves and deforms, larger voids are filled, the contact area between particles increases, resulting in attractive forces between atoms and enhanced mechanical cohesion between particles. 3 .
[0187] The compacted density of the positive electrode active material powder can be measured using methods and equipment known in the art. For example, it can be measured using a compaction density instrument, referring to GB / T 24533-2009. Specifically, a certain amount of positive electrode active material is placed on a compaction mold (the mold diameter is known). The mold is hollow in the middle and has a metal disc at the top and bottom. The positive electrode active material is placed between the metal discs, and a metal cylinder is placed on top. The mold is placed on a compaction density instrument, and the pressure is set to 3T. The thickness of the positive electrode active material under 3T pressure can be read on the instrument. The compacted density of the positive electrode active material powder is ρ = m / v, where v = (S × H), m is the mass of the positive electrode active material, and S is the bottom area of the mold (1.327 cm²). 2 H represents the thickness of the positive electrode active material after compaction.
[0188] In some embodiments, the compaction density of the positive electrode active material under 3T pressure can be selected as 2.55 g / cm³. 3 2.56 g / cm 3 2.57g / cm 3 2.58g / cm 3 2.59g / cm 3 2.60g / cm 3 2.61 g / cm 3 2.62 g / cm 3 2.63 g / cm 3 2.64 g / cm 3 2.65g / cm 3 2.66 g / cm 3 2.67 g / cm3 2.68g / cm 3 2.69 g / cm 3 2.70 g / cm 3 Or the range of values between any two.
[0189] The positive electrode active material particles have a good packing structure, so they can achieve a higher compaction density under pressure, providing a material basis for improving the compaction density of the electrode and preparing high-energy-density lithium-ion secondary batteries.
[0190] In some embodiments, the powder resistivity of the positive electrode active material at a pressure of 8 MPa is 0.5 Ω·cm-60.0 Ω·cm, and can be selected as 2.0 Ω·cm-40.0 Ω·cm.
[0191] The powder resistivity of the positive electrode active material can be measured using methods and equipment known in the art. For example, it can be measured using a powder resistivity meter (Suzhou Jingge, ST2722 type) according to GB / T 33822-2017. Specifically, a certain amount of positive electrode active material (e.g., 1g) is weighed and added to the feeding chamber of the powder resistivity meter. A pressure of 8MPa is applied, and the forward and reverse resistivity of the positive electrode active material are measured separately. The average value of the two is taken as the powder resistivity of the positive electrode active material.
[0192] In some embodiments, the powder resistivity of the positive electrode active material at a pressure of 8 MPa can be selected as 0.5 Ω·cm, 1 Ω·cm, 2 Ω·cm, 3 Ω·cm, 4 Ω·cm, 5 Ω·cm, 6 Ω·cm, 7 Ω·cm, 8 Ω·cm, 9 Ω·cm, 10 Ω·cm, 15 Ω·cm, 20 Ω·cm, 25 Ω·cm, 30 Ω·cm, 35 Ω·cm, 40 Ω·cm, 45 Ω·cm, 50 Ω·cm, 55 Ω·cm, 60 Ω·cm, or any value range between the two.
[0193] This positive electrode active material is produced by coating a carbon material on its surface, utilizing the spt properties of the surface carbon. 2 The structure facilitates rapid electron conduction between particles, resulting in low powder resistivity in the positive electrode active material. This is beneficial for improving the solid-phase electron transport rate and enhancing the battery's kinetic performance.
[0194] In some embodiments, the discharge specific capacity of the positive electrode active material at a 1C discharge rate is 135mAh / g-150mAh / g.
[0195] In this application, the positive electrode active material is assembled into a coin cell, and its electrical performance is tested using a blue electric current tester. At 25±5℃ and within a voltage range of 2.0V to 3.75V, it is charged at a constant current of 1C to 3.75V, paused for 5 minutes, charged at a constant voltage until the cutoff current reaches 50μA, and then discharged at a constant current of 1C to 2.0V. The discharge capacity of the coin cell is divided by the mass of the positive electrode active material to obtain the specific discharge capacity of the positive electrode active material at a 1C discharge rate at room temperature.
[0196] The preparation and testing process of the coin cell is as follows: 2.0g of positive electrode active material, conductive carbon black, and PVDF are mixed in a mass ratio of 0.9:0.05:0.05. Then, the organic solvent NMP (N-methylpyrrolidone) is added and thoroughly mixed. The mixture is then coated using a 150μm doctor blade, dried at 100℃ for 2 hours, and compacted to a density of 2.0g / cm³. 3 -2.2g / cm 3 Compact the positive electrode sheet, punch it into a 14mm diameter circle, weigh it and record the weight. Place the weighed positive electrode sheet in a vacuum drying oven (105℃, 1-12hrs, -90kPa). After drying, place the positive electrode sheet in a glove box. Assemble the battery in the following order: negative electrode shell - nickel mesh - lithium sheet - separator - positive electrode sheet - positive electrode shell. Add 65-87μL (pipette) of electrolyte (a 1:1 volume ratio of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) mixed solvent, with LiPF6 as the electrolyte). Place the negative electrode on top and put it in the groove of the sealing machine. The sealing pressure is 650kg / cm. 2 The button was removed with insulated tweezers, placed in a cleanroom bag, removed from the glove box, and left to stand in a constant temperature room for 3 hours to obtain the button for testing.
[0197] It is understandable that the discharge capacity of the positive electrode active material can also be obtained by disassembling the battery, obtaining the positive electrode sheet, assembling it into a coin cell according to the method described above, and then testing it.
[0198] In some embodiments, the discharge capacity of the positive electrode active material at a 1C discharge rate at room temperature can be selected as 135mAh / g, 140mAh / g, 145mAh / g, 150mAh / g, or any value range between the two.
[0199] The positive electrode active material exhibits a high discharge specific capacity at a 1C rate, indicating that it has good charge and discharge capabilities, which is beneficial for improving the battery's dynamic performance.
[0200] In some embodiments, the discharge capacity η of the positive electrode active material discharged to 3.2V accounts for ≥85%, where η is defined as follows: at room temperature, a coin cell containing the positive electrode active material is charged and discharged twice at a constant current of 0.1C within a voltage range of 2.0V to 3.75V, followed by a constant current charge and discharge once at a constant current of 1C. In the 1C charge and discharge test, the capacity value extracted at a discharge voltage of 3.2V is recorded as C1, and the capacity value extracted at a discharge voltage of 2.0V is recorded as C2, where η = C1 / C2. The charging process includes constant voltage charging, with a constant voltage of 3.75V and a constant voltage cutoff current of 50μA.
[0201] In some embodiments, the discharge capacity η of the positive electrode active material when discharged to 3.2V accounts for ≥88%.
[0202] The η value of the positive electrode active material can be measured using methods and equipment known in the art. As an example, a coin cell is first prepared according to the method described above. The prepared coin cell is then tested for electrical performance at room temperature using a blue-light tester. Specifically, the coin cell is charged and discharged twice at a constant current rate of 0.1C within a voltage range of 2.0V to 3.75V. After constant current charging to the cutoff voltage, it is charged at a constant voltage until the current reaches 50μA, followed by a single constant current charge and discharge at a rate of 1C. In the 1C charge and discharge test, the capacity value discharged from 3.75V to 3.2V is recorded as C1, and the capacity value discharged from 3.75V to 2.0V is recorded as C2, where η = C1 / C2.
[0203] In some implementations, η can be selected as 85%, 86%, 87%, 88%, 88.1%, 89%, 90%, 90.1%, 91%, 92%, 92.2%, 93%, 94%, 94.1%, 94.5%, 95%, 95.1%, or any range between the two.
[0204] In some embodiments, the discharge capacity percentage η of the positive electrode active material in the freshly prepared lithium-ion secondary battery when discharged to 3.2V is ≥88%. After the freshly prepared lithium-ion secondary battery is charged and discharged at a constant current rate of 0.1C within a voltage range of 2.0V to 3.75V for a period of time, the discharge capacity percentage η of the positive electrode active material when discharged to 3.2V can be maintained at ≥85%.
[0205] The high discharge capacity ratio of the positive electrode active material used in the lithium-ion secondary battery of this application to 3.2V indicates that the positive electrode active material has good kinetic performance. At the same time, the high η value indicates that the lithium-ion secondary battery containing the positive electrode active material still has a high voltage when discharged to a low state of charge (SOC), which is beneficial for maintaining good power performance.
[0206] In some embodiments, the positive electrode film layer further includes a conductive agent, the mass content of which is 0.01-1.5% based on the total mass of the positive electrode film layer.
[0207] In some embodiments, based on the total mass of the positive electrode film, the mass content of the conductive agent can be selected as 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, or any value range between the two.
[0208] In some embodiments, the conductive agent includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0209] Because the particles in this positive electrode film have formed a good stacking structure, the positive electrode active material particles are coated with a highly graphitized carbon layer on the surface and are in full contact with each other, resulting in good electronic conductivity. This reduces the amount of conductive agent used in the positive electrode film, which is beneficial to further increase the loading of the positive electrode active material and improve the energy density of the lithium-ion secondary battery.
[0210] In some embodiments, the positive electrode film layer further includes a binder, and based on the total mass of the positive electrode film layer, the mass content of the positive electrode active material is 92%-99.5%, optionally 96.5%-99.5%; the mass content of the binder is 0.5%-3%.
[0211] In some embodiments, the adhesive includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0212] In some embodiments, based on the total mass of the positive electrode film, the mass content of the positive electrode active material can be selected as 92%, 93%, 94%, 95%, 96%, 96.5%, 97%, 98%, 99%, 99.5%, or any range between the two.
[0213] In some embodiments, based on the total mass of the positive electrode film, the mass content of the binder can be selected as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or any value range between the two.
[0214] When the mass content of the positive electrode active material and the mass content of the binder are within the above range, the loading of active material in the positive electrode film layer per unit volume can be effectively increased, while maintaining good internal adhesion, reducing the probability of powder shedding, expansion and cracking, and improving the energy density of the secondary battery while taking into account safety performance.
[0215] In some embodiments, the one-sided density of the positive electrode film is 300 mg / 1540 mm². 2 -450mg / 1540mm 2 .
[0216] In this application, the unilateral density of the positive electrode film layer has a meaning known in the art and can be tested using methods known in the art. For example, take a positive electrode sheet that has been coated on one side and compacted (if it is a double-sided coated positive electrode sheet, the positive electrode film layer on one side can be wiped off first), cut it into small circular pieces with an area of S1, weigh them, and record their weight as M1. Then wipe off the positive electrode film layer of the above-weighed positive electrode sheet, weigh the current collector, and record it as M0. The unilateral density of the positive electrode film layer = (M1-M0) / S1. To ensure the accuracy of the test results, multiple sets (e.g., 10 sets) of samples can be tested, and the average value can be calculated as the test result.
[0217] In some embodiments, the areal density of the positive electrode film layer on one side may be selected as 300 mg / 1540 mm². 2 310mg / 1540mm 2 320mg / 1540mm 2 330mg / 1540mm 2 340mg / 1540mm 2 350mg / 1540mm 2 360mg / 1540mm 2 370mg / 1540mm 2 380mg / 1540mm 2 390mg / 1540mm 2 400mg / 1540mm 2 410mg / 1540mm 2 420mg / 1540mm 2 430mg / 1540mm 2 440mg / 1540mm 2 450mg / 1540mm 2 Or the range of values between any two.
[0218] Positive electrode films with areal densities within the above range can help improve the energy density of lithium-ion secondary batteries.
[0219] In some embodiments, the positive electrode film layer of the lithium-ion secondary battery, in its fully discharged state, has a compaction density of 2.52 g / cm³. 3 -2.78g / cm 3 .
[0220] In some embodiments, the positive electrode film layer of the lithium-ion secondary battery, in its fully discharged state, has a compaction density of 2.55 g / cm³. 3 -2.75g / cm 3 .
[0221] In this application, the fully discharged state refers to the state in which the battery is placed at 25°C, left to stand for 2 hours, and then discharged at a constant current of 1 / 3C to 2.5V and then discharged at a constant current of 0.1C to 2.0V.
[0222] The compaction density of the positive electrode film can be tested using methods known in the art. As an example, the battery is placed in a 25°C oven environment and left to stand for 2 hours. After the battery temperature is maintained at 25°C, the battery is discharged at a constant current of 1 / 3C to 2.5V and then discharged at a constant current of 0.1C to 2.0V. The battery is then disassembled to obtain the positive electrode sheet. The residual electrolyte is treated with dimethyl carbonate solvent, the electrode sheet is dried, and it is cut into small circular pieces with an area of S. The mass of the circular pieces is obtained as W1, and the thickness of the positive electrode sheet is measured using a micrometer. Then, the positive electrode film layer of the weighed electrode sheet is wiped off, the mass of the current collector is weighed and recorded as W2, and the thickness of the current collector is measured using a micrometer. Then, the compaction density of the positive electrode film layer PD = (W1-W2) / [(T1-T2)×S].
[0223] In some embodiments, the positive electrode film of the lithium-ion secondary battery, in its fully discharged state, has a compaction density of 2.52 g / cm³. 3 2.53g / cm 3 2.54 g / cm 3 2.55g / cm 3 2.56 g / cm 3 2.57g / cm 3 2.58g / cm 3 2.59g / cm 3 2.60g / cm 3 2.61 g / cm 3 2.62 g / cm 3 2.63 g / cm 3 2.64 g / cm 3 2.65g / cm 3 2.66 g / cm 3 2.67 g / cm 3 2.68g / cm3 2.69 g / cm 3 2.70 g / cm 3 2.71 g / cm 3 2.72 g / cm 3 2.73 g / cm 3 2.74 g / cm 3 2.75g / cm 3 2.76 g / cm 3 2.77 g / cm 3 2.78g / cm 3 Or the range of values between any two.
[0224] In some embodiments, the compaction density of the positive electrode film layer after the compaction process is 2.63 g / cm³. 3 -2.90g / cm 3 .
[0225] In some embodiments, the compaction density of the positive electrode film layer after the compaction process can be selected as 2.63 g / cm³. 3 2.64 g / cm 3 2.65g / cm 3 2.66 g / cm 3 2.67 g / cm 3 2.68g / cm 3 2.69 g / cm 3 2.70 g / cm 3 2.71 g / cm 3 2.72 g / cm 3 2.73 g / cm 3 2.74 g / cm 3 2.75g / cm 3 2.76 g / cm 3 2.77 g / cm 3 2.78g / cm 3 g / cm 3 2.79 g / cm 3 2.80g / cm 3 2.81 g / cm 3 2.82 g / cm 3 2.83 g / cm 3 2.84 g / cm 3 2.85g / cm 3 2.86 g / cm 3 2.87 g / cm 3 2.88g / cm 3 2.89 g / cm3 2.90g / cm 3 Or the range of values between any two.
[0226] In this application, "compaction" refers to the process of compacting the positive electrode film layer with mechanical pressure during battery assembly to improve its density and conductivity.
[0227] In some embodiments, the compaction density of the positive electrode film layer after formation processing is 2.52 g / cm³. 3 -2.78g / cm 3 .
[0228] In some embodiments, the compaction density of the positive electrode film layer after formation processing can be selected as 2.52 g / cm³. 3 2.53g / cm 3 2.54 g / cm 3 2.55g / cm 3 2.56 g / cm 3 2.57g / cm 3 2.58g / cm 3 2.59g / cm 3 2.60g / cm 3 2.61 g / cm 3 2.62 g / cm 3 2.63 g / cm 3 2.64 g / cm 3 2.65g / cm 3 2.66 g / cm 3 2.67 g / cm 3 2.68g / cm 3 2.69 g / cm 3 2.70 g / cm 3 2.71 g / cm 3 2.72 g / cm 3 2.73 g / cm 3 2.74 g / cm 3 2.75g / cm 3 2.76 g / cm 3 2.77 g / cm 3 2.78g / cm 3 Or the range of values between any two.
[0229] In this application, formation refers to the formation of a stable solid electrolyte interface (SEI film) and electrode structure through electrochemical reactions during the first charge and discharge of the battery.
[0230] It is understandable that, with the rebound of the electrode during the cycle, the compaction density of the positive electrode film in the fully discharged state of the lithium-ion secondary battery is slightly lower than that of the positive electrode film after compaction and formation.
[0231] A compaction density of the positive electrode film within the above-mentioned range is beneficial to improving the energy density of lithium-ion secondary batteries.
[0232] In some embodiments, the positive electrode film layer of the lithium-ion secondary battery, in its fully discharged state, has a compaction density of 2.52 g / cm³. 3 -2.78g / cm 3 In the cross-section along the thickness direction of the electrode sheet, the porosity of the positive electrode film is 10%-22%.
[0233] In some embodiments, the positive electrode film layer of the lithium-ion secondary battery, in its fully discharged state, has a compaction density of 2.55 g / cm³. 3 -2.75g / cm 3 In the cross-section along the thickness direction of the electrode sheet, the porosity of the positive electrode film is 10%-20%.
[0234] In some embodiments, when the lithium-ion secondary battery is in a fully discharged state, the porosity of the positive electrode film layer in the cross-section along the thickness direction of the electrode sheet can be selected as 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, or any value range between the two.
[0235] The porosity of the positive electrode film layer in a cross-section along the electrode thickness direction can be tested as follows: Import the scanning electron microscope (SEM) image of the positive electrode film layer in a cross-section along the electrode thickness direction obtained as described above into ImageJ software. Select the line tool and use a line to mark the length of the scale bar in the image. Click "Analyze Set Scale" and set the scale parameters in the software according to the scale bar length in the image. Select the rectangle tool and select the part of the image outside the scale bar area. Use "Image Duplicate" to copy the selected area and use "Image Type 8bit" to adjust the image format. Select "Analyze Set Measurements" and choose the following 5 options: "Area", "Mean gray value", "AreaFraction", "Limit to threshold", and "Feret's diameter". Select 3 for "Decimal places". Then select "Image" - "Adjust" - "Threshold" in sequence and set 0 and 100 in the selected position of "Threshold". You can then use the Analyze-Measure function to export the porosity data in the SEM image of this cross-section. Export using "Image" - "Overlay" - "Flatten" to obtain a pore image; click "Apply" in "Threshold", then click "Analyze" - "Analyze Particles", check the four columns on the left to obtain pore statistics.
[0236] like Figure 8 As shown, in this embodiment of the application, "pores" in the cross-section of the positive electrode film are identified through image color difference and threshold. These "pores" are not the pore data obtained from the venting test, but are mainly used to characterize the cross-sectional area between particles in the cross-section of the positive electrode film. This method is superior to the venting method because the porosity obtained by the venting method is related to the pores between particles and also to the pores in the carbon layer coating the surface of the lithium iron phosphate particles, thus failing to objectively reflect the pores between particles. The lower the porosity in the cross-section of the positive electrode film tested by this method, the better the particle gradation of the positive electrode film and the higher the compaction density. Furthermore, under the same gradation and roller pressure, a lower porosity means that particles are more likely to slide against each other, thereby reducing the risk of overpressure and stress concentration in the film, further reducing the probability of the positive electrode film demolding during long cycles, and improving the long-cycle performance of the battery.
[0237] In some embodiments, the positive electrode sheet includes a base coating layer disposed between the positive electrode film layer and the positive electrode current collector; the base coating layer includes carbon-based particles, and the distribution density of carbon-based particles with a particle size greater than 100 nm in the base coating layer is ≤10 pcs / 10 μm.
[0238] Carbon-based particles refer to particles whose main component is carbon, including but not limited to conductive carbon and carbon black.
[0239] The undercoat layer helps improve the conductivity and adhesion between the positive electrode film and the current collector, reduces the likelihood of the positive electrode film detaching from the current collector during cycling, and improves the battery's dynamic performance. In the high compaction density electrode sheets of this application embodiment, for example, the compaction density of the positive electrode sheet in its fully loaded state is greater than or equal to 2.4 g / cm³. 3 At this time, the current collector is easily damaged during the high-pressure compaction process of the electrode sheet, and large-sized particles are prone to creating pits on the current collector. Controlling the distribution density of carbon-based particles with a particle size greater than 100nm in the bottom coating layer to ≤10pcs / 10μm is beneficial to reducing the probability of damage to the current collector in the high-pressure compaction electrode sheet and further improving the ultimate compaction density of the positive electrode sheet.
[0240] The distribution density of carbon-based particles with a diameter greater than 100 nm in the undercoat can be determined by the method described above. The positive electrode film is cut along the thickness direction of the electrode by an argon ion beam, and scanning electron microscope or microscopic image is taken. The size of carbon particles in the undercoat is detected by statistical methods, and the number of carbon-based particles with a diameter greater than 100 nm per 10 μm in the undercoat is counted. The count is repeated at least 5 times and the average value is calculated.
[0241] The base coating in this embodiment can be achieved through any known preparation process, such as pre-sieving or centrifuging during the preparation of carbon-based particles to remove large carbon-based material particles, thereby reducing the D of the carbon-based particles added during the preparation of the base coating. V50 In the 20-60nm range, D V90 For materials with a wavelength of 70 nm or less, a base coating is obtained by mixing, stirring, and applying the carbon-based material with a binder onto the current collector.
[0242] In some embodiments, the compacted density of the positive electrode sheet in its fully loaded state is greater than or equal to 2.4 g / cm³. 3 The thickness of the base coating layer on one side is 1μm-4μm.
[0243] In some embodiments, the compacted density of the positive electrode sheet in its fully loaded state is greater than or equal to 2.5 g / cm³. 3 The thickness of the base coating layer on one side is 2μm-4μm.
[0244] As the compaction density of the electrode increases, the compressive effect of large lithium phosphate particles (e.g., particles larger than 1 μm) on the undercoat becomes more significant. Therefore, stress concentration easily occurs at large particle sites, and these particles can even penetrate the undercoat and damage the current collector. Increasing the thickness of the undercoat helps to mitigate stress concentration in the electrode, further improving the electrode's ultimate compaction density.
[0245] The thickness of the base coating on one side can be tested as follows: As described above, the positive electrode film is cut along the thickness direction of the electrode using an argon ion beam, and a scanning electron microscope image is taken. The thickness of the base coating on one side is measured at 1m intervals along the length of the electrode. After measuring the thickness of the base coating at 10 points, the average value is calculated. It is important to note that outliers should be avoided during the measurement process, namely, areas with a thickness less than 50nm and areas with a thickness greater than 4m. These outliers are mainly due to extreme thickness fluctuations in individual areas caused by abnormal stress concentration and compression during electrode compaction, and are not statistically significant.
[0246] In some embodiments, the thickness of the positive current collector is less than or equal to 17 μm, and can be selected as 13 μm-15 μm.
[0247] In some embodiments, the thickness of the positive current collector is 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, or any value between the two.
[0248] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0249] In some embodiments of the lithium-ion secondary battery, the negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector, wherein the areal density of the negative electrode film layer on one side is 140 mg / 1540 mm². 2 -215mg / 1540mm 2 ; and / or the compaction density of the negative electrode film is 1.40 g / cm³. 3 -1.75g / cm 3 .
[0250] The unilateral density and compaction density of the negative electrode film can be tested using a method similar to that used for the positive electrode film described above.
[0251] Having the areal density and compaction density of the negative electrode film within the above-mentioned range is beneficial for improving the energy density of lithium-ion secondary batteries.
[0252] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0253] In some embodiments, the negative electrode film layer includes a negative electrode active material. The negative electrode active material may be any negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0254] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0255] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0256] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0257] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, compaction and other processes.
[0258] In some embodiments, the lithium-ion secondary battery includes an electrolyte. The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte, which can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or entirely solid-state.
[0259] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0260] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0261] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0262] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0263] In some embodiments, the lithium-ion secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0264] In some embodiments, the diaphragm material can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0265] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0266] In some embodiments, the lithium-ion secondary battery may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.
[0267] In some implementations, the outer packaging of the lithium-ion secondary battery can be a hard shell, such as a hard plastic shell, aluminum shell, or steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0268] The second aspect of this application provides a battery device including the lithium-ion secondary battery provided in the first aspect of this application. The battery device includes at least one of a battery module, a battery pack, and an energy storage battery.
[0269] A third aspect of this application provides an electrical device, including the lithium-ion secondary battery provided in the first aspect of this application.
[0270] This application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0271] As the electrical device, a secondary battery, battery module, or battery pack can be selected according to its usage requirements.
[0272] Figure 7 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.
[0273] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a rechargeable battery as their power source.
[0274] A fourth aspect of this application provides a method for preparing a positive electrode active material, comprising: obtaining a first positive electrode active material component and a second positive electrode active material component; mixing the first positive electrode active material component and the second positive electrode active material component, adding a carbon source to obtain a mixed positive electrode active material component; subjecting the mixed positive electrode active material component to a third sintering to obtain a sintered product, and crushing the sintered product to obtain a positive electrode active material; wherein, the first positive electrode active material component has a D... V50 The D of the second positive electrode active material component is 0.35μm-0.45μm. V50 The thickness is 0.25μm-0.35μm, and the mass ratio of the first positive electrode active material component to the second positive electrode active material component is (60:40)-(70:30).
[0275] The preparation method provided in this application combines two positive electrode active materials with small particle sizes and then sintersects them again. To obtain particles with a particle size R1 satisfying 1.5 μm ≤ R1 < 5 μm, the area percentage of these particles is 10.0%-20.0%; particles with a particle size R2 satisfying 50 nm ≤ R2 < 200 nm, the area percentage of these particles is 5.0%-12.0%; and particles with a particle size R3 satisfying 200 nm ≤ R3 < 1.5 μm, the area percentage of these particles is 73.0%-80.0%. The particle size distribution (D) of the particles satisfying R3 is... A90 -D A10 ) / D A50 This provides a material basis for the preparation of positive electrode films with a thickness of 1.40-1.683.
[0276] In some embodiments, the preparation method of the first positive electrode active material includes: obtaining a first mixed raw material comprising a first carbon source, a first lithium source, a first iron source, a first phosphorus source and a solvent; grinding the first mixed raw material to obtain a first mixed slurry; drying the first mixed slurry to obtain a first precursor powder; and sintering the first precursor powder to obtain the first positive electrode active material.
[0277] In some embodiments, the preparation method of the second positive electrode active material includes: obtaining a second mixed raw material comprising a second carbon source, a second lithium source, a second iron source, a second phosphorus source and a solvent; grinding the second mixed raw material to obtain a second mixed slurry; drying the second mixed slurry to obtain a second precursor powder; and sintering the second precursor powder to obtain the second positive electrode active material.
[0278] In some embodiments, the iron source is an iron-containing compound. In some embodiments, the iron source includes at least one of ferric hydroxide, ferrous chloride, ferric oxide, ferric phosphate, ferric pyrophosphate, ferrous oxalate, iron powder, ferric nitrate, magnetite, and ferric hydroxide.
[0279] In some embodiments, the phosphorus source is a phosphoric acid compound. In some embodiments, the phosphorus source includes at least one selected from phosphoric acid, ferric phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.
[0280] In some embodiments, the iron source and the phosphorus source can be the same substance. In some embodiments, ferric phosphate is used as both the iron source and the phosphorus source.
[0281] In some embodiments, the lithium source includes one or more of lithium carbonate, lithium dihydrogen phosphate, lithium oxalate, lithium oxide, lithium hydroxide, and lithium acetate.
[0282] In some embodiments, the lithium source includes lithium carbonate.
[0283] In some embodiments, the carbon source includes one or more of glucose, polyethylene glycol, citric acid, sucrose, starch, fructose, lactose, polyaniline, polyacrylonitrile, and polyvinylpyrrolidone.
[0284] In some embodiments, the carbon source includes glucose and polyethylene glycol.
[0285] In some implementations, the mass content of polyethylene glycol is 20%-75% based on the total mass of the carbon source.
[0286] The polymer carbon source has a relatively low graphitization temperature, which allows the carbon coating layer on the surface of the positive electrode active material to decompose and form a carbon layer at a lower sintering temperature. This hinders the growth and sintering of lithium transition metal phosphate grains, which is beneficial for reducing the particle size of the positive electrode active material.
[0287] Meanwhile, polymer carbon sources typically have high molecular weights or long molecular chains, which are easy to form stable framework structures through cross-linking or orientation during heat treatment. This orderliness is preserved during high-temperature carbonization, which is beneficial for the directional growth of graphite crystals. At the same time, the entanglement and cross-linking between long chains help reduce structural defects and reduce lattice disorder caused by chain breakage during carbonization, thereby improving the degree of graphitization.
[0288] Organic molecules in carbon sources decompose at high temperatures, releasing carbon atoms. These carbon atoms can cover and fill tiny gaps or defects on the surface of active materials, reducing surface roughness. The coating layer formed by sugar carbon sources has a low degree of graphitization and a loose flocculent carbon structure, which may itself act as a new roughness point. Therefore, the higher the proportion of polymer carbon sources in the carbon source, the more beneficial it is to optimizing the surface roughness of the positive electrode active material.
[0289] In some embodiments, the slurry further includes a titanium source, optionally including one or more of titanium dioxide, tetrabutyl titanate, titanium nitrate, and titanic acid.
[0290] Titanium sources often have low surface activity. Including titanium sources in the slurry can reduce the activity of lithium transition metal phosphate precursors and inhibit the particle growth of lithium transition metal phosphates during high-temperature sintering, resulting in smaller particles of lithium transition metal phosphates during sintering.
[0291] Titanium is used as a lattice stabilizer; the element titanium is usually represented by Ti. 4+ In the form of lithium transition metal phosphate, some titanium ions can replace iron ions in the crystal lattice, making the crystal structure more stable and reducing the possibility of lithium and iron ions being reversed, especially at high temperatures or during high-current charging and discharging.
[0292] Meanwhile, titanium doping helps improve the sphericity of the particles and reduce their roughness, thereby enhancing the overall structural stability of the material.
[0293] In some embodiments, the atomic molar ratio of iron to phosphorus in the iron source and the phosphorus source is 0.95-1.
[0294] In some embodiments, the atomic molar ratio of iron to phosphorus in the lithium source and the iron source can be selected as 0.95, 0.955, 0.96, 0.965, 0.97, 0.975, 0.98, 0.985, 0.99, 0.995, 1, or any value range between the two.
[0295] In the synthesis of lithium-containing transition metal oxides, the iron-to-phosphorus ratio affects the reaction rate and crystal growth process. A low iron-to-phosphorus ratio can increase the reaction rate of the iron source, accelerating its conversion into lithium-containing transition metal phosphates; a high phosphorus content can suppress the interaction between iron and carbon, reducing the formation of iron-based compounds such as Fe3C, which is conducive to the graphitization of the carbon layer. This step becomes the rate-controlling step, extending the crystal growth time and promoting the formation of larger particles. This allows for the control of the particle size and area distribution, resulting in the desired packing structure.
[0296] In some embodiments, the solvent includes water and mixtures thereof.
[0297] In some embodiments, obtaining a first mixed raw material comprising a first carbon source, a first lithium source, a first iron source, a first phosphorus source, and a solvent includes: adding the first carbon source, the first lithium source, the first phosphorus source, the first iron source, and the first carbon source to a solvent and mixing and stirring, wherein the stirring speed is 1400 rpm to 2200 rpm.
[0298] In some embodiments, the first mixed raw materials are ground to obtain a first mixed slurry, wherein the grinding satisfies one or more of the following conditions:
[0299] (1) The grinding balls are one or more of the following: zirconium oxide balls, silicon nitride zirconium balls, and ceramic zirconium balls;
[0300] (2) The diameter of the grinding ball is 0.25mm-0.35mm;
[0301] (3) The grinding speed is 470rpm-530rpm;
[0302] (4) The grinding time is 3.0h-5.0h;
[0303] (5) The grinding chamber pressure is 0.01MPa-0.3MPa.
[0304] In some embodiments, obtaining a first precursor powder after drying the first mixed slurry includes spray drying.
[0305] In some embodiments, the first precursor powder undergoes a first sintering to obtain a first positive electrode active material, wherein the first sintering satisfies one or more of the following conditions:
[0306] (1) The heating rate is 2℃ / min-10℃ / min;
[0307] (2) The heat preservation temperature is 765℃-795℃;
[0308] (3) The heat preservation time is 6h-12h.
[0309] In some embodiments, obtaining a second mixed raw material comprising a second carbon source, a second lithium source, a second iron source, a second phosphorus source, and a solvent includes: adding the second carbon source, the second lithium source, the second iron source, and the second phosphorus source to the solvent and mixing and stirring, wherein the stirring speed is 1400 rpm-2200 rpm.
[0310] In some embodiments, the second mixed raw material is ground to obtain a second mixed slurry, wherein the grinding satisfies one or more of the following conditions:
[0311] (1) The grinding balls are one or more of the following: zirconium oxide balls, silicon nitride zirconium balls, and ceramic zirconium balls;
[0312] (2) The diameter of the grinding ball is 0.25mm-0.35mm;
[0313] (3) The grinding speed is 470rpm-530rpm;
[0314] (4) The grinding time is 4.0h-6.0h;
[0315] (5) The grinding chamber pressure is 0.01MPa-0.3MPa.
[0316] In some embodiments, obtaining a second precursor powder after drying the second mixed slurry includes spray drying.
[0317] In some embodiments, the second precursor powder undergoes a second sintering to obtain a second positive electrode active material, wherein the second sintering satisfies one or more of the following conditions:
[0318] (1) The heating rate is 2℃ / min-10℃ / min;
[0319] (2) The heat preservation temperature is 705℃-735℃;
[0320] (3) The heat preservation time is 6h-12h.
[0321] In some embodiments, the first positive electrode active material component and the second positive electrode active material component are mixed, and a carbon source is added to obtain a mixed positive electrode active material component, wherein the carbon source includes glucose and polyethylene glycol.
[0322] In some embodiments, based on the total mass of the first positive electrode active material component and the second positive electrode active material component, the mass content of glucose in the mixed positive electrode active material component is 4.0%-6.0%, and the mass content of polyethylene glycol is 4.0%-6.0%.
[0323] In some embodiments, the D of the first positive electrode active material component grinding product V50 The range is 0.35μm-0.45μm.
[0324] In some embodiments, the D of the milled product of the second positive electrode active material component V50 The range is 0.25μm-0.35μm.
[0325] Controlling the grinding particle size to a smaller value is beneficial for the particles to form a product with a higher proportion of the R2 particle size range during the subsequent sintering process.
[0326] In some embodiments, the mass ratio of the first positive electrode active material component to the second positive electrode active material component is (60:40)-(70:30).
[0327] By controlling the mass ratio of the first positive electrode active material component and the second positive electrode active material component, the area ratio and distribution of particles of different sizes can be precisely controlled to obtain the desired packing structure.
[0328] In some embodiments, the mixed positive electrode active material components undergo a third sintering to obtain the sintered product.
[0329] In some embodiments, the third sintering satisfies one or more of the following conditions:
[0330] (1) The heat preservation temperature is 760℃-790℃;
[0331] (2) The heat preservation time is 6h-12h;
[0332] (3) The heating rate is 2℃ / min-10℃ / min.
[0333] By controlling the first and second sintering processes, the final particle size and distribution of the first and second positive electrode active materials can be affected. This effectively shortens the sintering time in the high-temperature range of the third sintering process involving the mixed positive electrode active materials, preventing abnormal particle growth and grain coarsening caused by excessively long sintering times. Adjusting the particle size of the two grinding processes during the second sintering process controls the particle activity, resulting in a larger area of the positive electrode active material that meets the R2 particle size requirement. This improves the electrode compaction density, enhances the energy density of the battery cell, and simultaneously improves the cycle performance of the battery cell.
[0334] In some embodiments, the sintered product is subjected to air jet milling to obtain the positive electrode active material.
[0335] In some embodiments, the grading frequency of the air jet mill is 18Hz-24Hz, and the milling pressure is 0.45MPa-0.65MPa.
[0336] In air jet milling, the classification frequency refers to the operating frequency of the classification device, which is typically related to the classification efficiency and particle size distribution. A higher classification frequency results in more frequent sieving of particles in the airflow, removing larger particles and leaving smaller ones. Furthermore, a higher classification frequency may increase the number of particle collisions, subjecting irregular particles to further impact, resulting in smoother particle surfaces and a more spherical shape.
[0337] High air pressure causes particles to be subjected to greater impact force, and the collisions between particles are more intense. This results in stronger impact and wear on the particle surface, which can crush large particles into smaller particles. The more intense collisions between particles make the surface easier to be trimmed, improving the sphericity and surface smoothness of the particles.
[0338] However, excessively high classification frequency and pulverizing pressure can cause agglomerated particles to disperse into primary particles, leading to further cracking and breakage. This affects the intended particle size distribution, results in an incomplete carbon coating, negatively impacts particle slippage during rolling, and increases the contact and reaction between lithium-containing transition metal phosphates and external factors such as the electrolyte, which is detrimental to battery cycle performance and lifespan. Therefore, it is necessary to control the classification frequency and pulverizing pressure of the airflow pulverizer within a suitable range.
[0339] The fifth aspect of this application provides a method for preparing a positive electrode sheet, the method comprising sequentially adding a binder, a conductive agent, and a positive active material prepared by the method of the fourth aspect, dry mixing them, adding a solvent, stirring, adjusting the viscosity, and obtaining a slurry; transferring the slurry to at least one side of a positive current collector, drying, and hot pressing to obtain a positive electrode film layer.
[0340] In some embodiments, the viscosity of the shipped slurry is 8000 Pa·s-12000 Pa·s.
[0341] In some embodiments, the hot pressing includes at least three hot roller pressings, with the hot roller pressure increasing sequentially to 20-50 tons, 50-70 tons, and 70-90 tons; the hot roller temperature is 40℃-80℃, and the positive electrode sheet is heated to 40℃-50℃ before the first hot roller compaction.
[0342] The positive electrode active material prepared by the above-mentioned shipping viscosity, hot pressing process and preparation method in the fourth aspect of this application is beneficial to further reduce the cross-sectional porosity of the positive electrode film, increase the ultimate compaction density of the electrode sheet and improve the energy density of the battery.
[0343] Example
[0344] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0345] Example 1
[0346] (1) Preparation of positive electrode active material:
[0347] Preparation of the first positive electrode active material component:
[0348] Lithium carbonate, iron phosphate, glucose, polyethylene glycol, and titanium dioxide were added to water and mixed in a premixing tank at 1800 rpm. The mixture was then demagnetized using a demagnetizing rod with a magnetic field strength of 8000-12000 Gs to obtain the first mixed raw material. The iron phosphate used consisted of first and second iron phosphate with iron-to-phosphorus ratios of 0.965 and 0.975, respectively, with a mass ratio of 2:1. The glucose and polyethylene glycol had a mass ratio of 1:1. The addition amount resulted in a finished product with a carbon content of 1.1%. The titanium dioxide doping amount resulted in a titanium content of 3000 ppm in the carbon-coated lithium iron phosphate cathode active material. The first mixed raw material was then ground in a sand mill to obtain D...V50 The particle size of the first mixed slurry is 0.40 μm; the first mixed slurry is spray-dried to obtain the first precursor powder, the first precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 780°C at a heating rate of 5°C / min and held for 10 h, and after cooling, it is crushed by air jet milling to obtain the first positive electrode active material component.
[0349] The second group of positive electrode active materials was prepared as follows:
[0350] Lithium carbonate, iron phosphate, glucose, polyethylene glycol, and titanium dioxide were added to water and mixed in a premixing tank at 1800 rpm. The mixture was then demagnetized using a demagnetizing rod with a magnetic field strength of 8000-12000 Gs to obtain a second mixed raw material. The iron-to-phosphorus ratio of iron phosphate was 0.965, and the mass ratio of glucose to polyethylene glycol was 1:1. The addition amount resulted in a carbon content of 1.1% in the finished product. The titanium dioxide doping amount resulted in a titanium content of 5000 ppm in the carbon-coated lithium iron phosphate cathode active material. The second mixed raw material was then milled in a sand mill to obtain D... V50 The particle size of the second mixed slurry is 0.30 μm. The second mixed slurry is spray-dried to obtain the second precursor powder. The second precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 720°C at a heating rate of 5°C / min, and held at that temperature for 10 h. After cooling, it is crushed by air jet milling to obtain the second positive electrode active material component.
[0351] The first and second positive electrode active material components were mixed at a mass ratio of 65:35 to obtain a mixed positive electrode active material component. Simultaneously, titanium dioxide and glucose and polyethylene glycol at a mass ratio of 1:1 were added. The amount of titanium dioxide added resulted in a titanium content of 2000 ppm in the final product, and the amount of glucose and polyethylene glycol added resulted in a carbon content of 0.15% in the final product. After uniform mixing, the mixed positive electrode active material component was sintered in a nitrogen atmosphere, with the temperature increased from 25°C to 770°C at a rate of 3°C / min and held for 10 hours. After cooling, the sintered product was obtained. The sintered product was then crushed using an air jet milling method to obtain carbon-coated lithium iron phosphate positive electrode active material.
[0352] The prepared positive electrode active material has a carbon content of 1.254% by mass, a lithium iron antisite defect concentration of 0.31%, and a powder tap density of 1.25 g / cm³. 3 The compacted density of the powder under 3T pressure is 2.62 g / cm³. 3The powder resistivity at 8 MPa pressure is 12.14 Ω·cm; the discharge capacity at 1C discharge rate is 143.5 mAh / g; and the discharge capacity at 3.2V discharge platform accounts for 90.16%.
[0353] (2) Preparation of the positive electrode sheet:
[0354] 2.2 wt% PVDF, 0.8 wt% conductive carbon black, and 97.0 wt% positive electrode active material were sequentially added and dry-mixed, followed by the addition of N-methylpyrrolidone. The mixture was stirred and the viscosity adjusted to obtain a slurry. This slurry was then transferred and coated onto a base coating of current collector aluminum foil. The base coating consisted of carbon black and PVDF in a 1:1 mass ratio. The density of carbon-based particles larger than 100 nm in the base coating was ≤10 pcs / 10 μm, and the base coating thickness was 2 μm. After drying and hot pressing, a single-sided surface density of 350 mg / 1540 mm² was obtained. 2 The positive electrode film layer. The viscosity of the shipped slurry is 10000 Pa·s.
[0355] The hot pressing process includes three hot roller pressing processes, with the hot roller pressing pressure increasing sequentially to 45 tons, 55 tons, and 80 tons. The hot roller temperature is 70℃. Before the first hot roller compaction, the electrode sheet is heated to 45℃.
[0356] The compaction density of the positive electrode sheet is the ultimate compaction density of the positive electrode sheet. The test method for the ultimate compaction density of the positive electrode sheet is described below; in this example, the ultimate compaction density of the positive electrode sheet is 2.73 g / cm³. 3 .
[0357] In the cross-section along the thickness direction of the prepared positive electrode film, 14,731 particles were counted. The results show that particles with a diameter of 1.5 μm ≤ R1 < 5 μm account for 15.45% of the area, particles with a diameter of 50 nm ≤ R2 < 200 nm account for 8.33%, and particles with a diameter of 200 nm ≤ R3 < 1.5 μm account for 76.22%. The particle size distribution (D) of particles satisfying R3 is also significant. A90 -D A10 ) / D A50 It is 1.538.
[0358] The median C of the graphitization degree of the positive electrode film obtained in laser microscopy confocal Raman spectroscopy instrument scanning mode. 50 The value is 1.04. In the cumulative distribution curve of the particle spheroidity area obtained from a cross-section along the electrode thickness direction, the median L of spheroidity is... A50 The median L of sphericity for particles with a sphericity of 0.739 and a sphericity of 1.5μm≤R1<5μm is 0.739. R1A50The median L of sphericity for particles with a value of 0.730 and a sphericity of 50nm ≤ R² < 200nm is given. R2A50 The median L of sphericity for particles with a sphericity of 0.758 and a sphericity of 200 nm ≤ R3 < 1.5 μm. R3A50 It is 0.734.
[0359] (3) Preparation of negative electrode sheet:
[0360] A mixture of 95.5 wt% negative electrode active material (artificial graphite), 1.0 wt% conductive agent (conductive carbon black), 2.0 wt% binder (styrene-butadiene rubber (SBR)), and 1.5 wt% thickener (sodium carboxymethyl cellulose (CMC)) was prepared by mixing with deionized water and stirring to disperse the mixture into a negative electrode slurry. The negative electrode slurry was then coated onto both sides of a Cu foil. After coating both sides, the foil was dried, compacted, slit, and sheeted to obtain the negative electrode sheet. The density of the coating on one side was 166 mg / 1540.25 mm². 2 The compacted density is 1.60 g / cm³. 3 .
[0361] (4) Preparation of the diaphragm:
[0362] Polypropylene membrane is used as the diaphragm.
[0363] (5) Preparation of electrolyte:
[0364] In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate (EC) and dimethyl carbonate (DMC) organic solvents were mixed evenly at a volume ratio of 1 / 1. Lithium salt LiPF6 was added and dissolved in the organic solvent. The concentration of LiPF6 in the solution was 1 mol / L. The mixture was stirred evenly to obtain the electrolyte.
[0365] (6) Battery fabrication:
[0366] The positive electrode, separator, and negative electrode are stacked in sequence. The separator should be able to isolate the positive and negative electrodes. The bare cell is obtained by winding. The bare cell is placed in the outer packaging, electrolyte is injected, and it goes through processes such as encapsulation, formation, and degassing to finally obtain a lithium-ion battery.
[0367] The preparation method of Example 2 is basically the same as that of Example 1. The difference is that in the preparation of the first positive electrode active material component, iron phosphate is used with iron-phosphorus ratios of 0.965 and 0.975, respectively, with a mass ratio of 3:1; the first precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 790°C at a heating rate of 5°C / min, and held at that temperature for 10 hours.
[0368] The preparation method of Example 3 is basically the same as that of Example 1. The difference is that in the preparation of the first positive electrode active material component, iron phosphate is used with iron-phosphorus ratios of 0.965 and 0.975, respectively, with a mass ratio of 1:1; the first precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 770°C at a heating rate of 5°C / min, and held at that temperature for 10 hours.
[0369] The preparation method of Example 4 is basically the same as that of Example 1, except that in the preparation of the first positive electrode active material component, iron phosphate is prepared using two different iron-to-phosphorus ratios of 0.965 and 0.975, with a mass ratio of 3:1; the first mixed raw material is ground in a sand mill to obtain D. V50 The particle size of the first mixed slurry is 0.35 μm; the first precursor powder is sintered in a nitrogen atmosphere, heated from 25 °C to 795 °C at a heating rate of 5 °C / min, and held at that temperature for 10 h.
[0370] The preparation method of Example 5 is basically the same as that of Example 1, except that in the preparation of the first positive electrode active material component, iron phosphate is prepared using two different iron-to-phosphorus ratios of 0.965 and 0.975, with a mass ratio of 1:1; the first mixed raw material is ground in a sand mill to obtain D. V50 The particle size of the first mixed slurry is 0.45 μm; the first precursor powder is sintered in a nitrogen atmosphere, heated from 25 °C to 765 °C at a heating rate of 5 °C / min, and held at that temperature for 10 h.
[0371] The preparation method of Example 6 is basically the same as that of Example 1, except that in the preparation of the second positive electrode active material component, the second precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 710°C at a heating rate of 5°C / min, and held at that temperature for 10 hours; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 60:40 to obtain a mixed positive electrode active material component.
[0372] The preparation method of Example 7 is basically the same as that of Example 1, except that in the preparation of the second positive electrode active material component, the second precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 730°C at a heating rate of 5°C / min, and held at that temperature for 10 hours; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 70:30 to obtain a mixed positive electrode active material component.
[0373] The preparation method of Example 8 is basically the same as that of Example 1, except that in the preparation of the second positive electrode active material component, the second mixed raw material is milled in a sand mill to obtain D. V50The particle size of the second mixed slurry is 0.35 μm; the second precursor powder is sintered in a nitrogen atmosphere, heated from 25 °C to 705 °C at a heating rate of 5 °C / min, and held at that temperature for 10 h; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 60:40 to obtain a mixed positive electrode active material component.
[0374] The preparation method of Example 9 is basically the same as that of Example 1, except that in the preparation of the second positive electrode active material component, the second mixed raw material is milled in a sand mill to obtain D. V50 The particle size of the second mixed slurry is 0.25 μm; the second precursor powder is sintered in a nitrogen atmosphere, heated from 25 °C to 735 °C at a heating rate of 5 °C / min, and held at that temperature for 10 h; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 70:30 to obtain a mixed positive electrode active material component.
[0375] The preparation method of Example 10 is basically the same as that of Example 1, except that in the preparation of the first positive electrode active material component, iron phosphate is prepared using two different iron-to-phosphorus ratios of 0.965 and 0.975, with a mass ratio of 3:1; the first mixed raw material is ground in a sand mill to obtain D. V50 The first mixed slurry has a particle size of 0.35 μm; the first precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 795°C at a heating rate of 5°C / min, and held at that temperature for 10 hours; in the preparation of the second positive electrode active material component, the second mixed raw material is sand-milled in a sand mill to obtain D. V50 The particle size of the second mixed slurry is 0.35 μm; the second precursor powder is sintered in a nitrogen atmosphere, heated from 25 °C to 705 °C at a heating rate of 5 °C / min, and held at that temperature for 10 h; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 60:40 to obtain a mixed positive electrode active material component.
[0376] The preparation method of Example 11 is basically the same as that of Example 1, except that in the preparation of the first positive electrode active material component, iron phosphate is prepared using two iron-to-phosphorus ratios of 0.965 and 0.975, with a mass ratio of 1:1; the first mixed raw material is ground in a sand mill to obtain D. V50 The first mixed slurry has a particle size of 0.45 μm; the first precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 765°C at a heating rate of 5°C / min, and held at that temperature for 10 h; in the preparation of the second positive electrode active material component, the second mixed raw material is sand-milled in a sand mill to obtain D. V50The particle size of the second mixed slurry is 0.25 μm; the second precursor powder is sintered in a nitrogen atmosphere, heated from 25 °C to 735 °C at a heating rate of 5 °C / min, and held at that temperature for 10 h; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 70:30 to obtain a mixed positive electrode active material component.
[0377] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that only iron phosphate with an iron-to-phosphorus ratio of 0.965 is used in the preparation of the first positive electrode active material component; the first mixed raw material is ground in a sand mill to obtain D. V50 The first mixed slurry has a particle size of 0.35 μm; the first precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 800°C at a heating rate of 5°C / min, and held at that temperature for 10 h; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 75:25 to obtain a mixed positive electrode active material component.
[0378] The preparation method of Comparative Example 2 is basically the same as that of Example 1, except that in the preparation of the first positive electrode active material component, iron phosphate is prepared using two different iron-to-phosphorus ratios of 0.965 and 0.975, with a mass ratio of 1:1; the first mixed raw material is ground in a sand mill to obtain D. V50 The first mixed slurry has a particle size of 0.45 μm; the first precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 750°C at a heating rate of 5°C / min, and held at that temperature for 10 h; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 62:38 to obtain a mixed positive electrode active material component.
[0379] The preparation method of Comparative Example 3 is basically the same as that of Example 1, except that in the preparation of the second positive electrode active material component, the second mixed raw material is milled in a sand mill to obtain D. V50 The particle size of the second mixed slurry is 0.35 μm; the second precursor powder is sintered in a nitrogen atmosphere, heated from 25 °C to 705 °C at a heating rate of 5 °C / min, and held at that temperature for 10 h; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 55:45 to obtain a mixed positive electrode active material component.
[0380] The preparation method of Comparative Example 4 is basically the same as that of Example 1, except that in the preparation of the second positive electrode active material component, the second mixed raw material is milled in a sand mill to obtain D. V50The particle size of the second mixed slurry is 0.25 μm; the second precursor powder is sintered in a nitrogen atmosphere, heated from 25 °C to 740 °C at a heating rate of 5 °C / min, and held at that temperature for 10 h; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 75:25 to obtain a mixed positive electrode active material component.
[0381] The preparation method of Comparative Example 5 is basically the same as that of Example 1, except that in the preparation of the first positive electrode active material component, iron phosphate is prepared using two iron-to-phosphorus ratios of 0.965 and 0.975, with a mass ratio of 1:3; the first precursor powder is sintered in a nitrogen atmosphere, heated from 25°C to 765°C at a heating rate of 5°C / min, and held at that temperature for 10 hours; in the preparation of the second positive electrode active material component, the second mixed raw material is milled in a sand mill to obtain D. V50 The particle size of the second mixed slurry is 0.25 μm; the second precursor powder is sintered in a nitrogen atmosphere, heated from 25 °C to 735 °C at a heating rate of 5 °C / min, and held at that temperature for 10 h; the first positive electrode active material component and the second positive electrode active material component are mixed at a mass ratio of 65:35 to obtain a mixed positive electrode active material component.
[0382] Performance testing
[0383] 1. Ultimate compaction density of electrode sheets
[0384] The double-coated electrode sheets were compacted using a roller press, and the elongation and flexibility of the compacted electrode sheets were tested. By increasing the pressure of the roller press, electrode sheets with different compaction densities were obtained. As the pressure increased, the compaction density of the electrode sheet increased, the elongation of the electrode sheet increased, and the flexibility of the electrode sheet decreased. Excessive elongation of the electrode sheet can easily lead to warping, while insufficient flexibility can easily lead to brittle fracture. Therefore, the lower of the compaction density corresponding to an elongation of 8% or the compaction density corresponding to a flexible folding number of times is defined as the ultimate compaction density of the electrode sheet.
[0385] The compaction density is calculated by dividing the mass of the positive electrode film by the volume of the positive electrode film.
[0386] The method for testing elongation is as follows:
[0387] Lay the electrode flat on a horizontal table and cut it into sections, each about 100cm long. Remove the copper foil from the edges of the electrode, ensuring the cut edges are parallel to the MD direction (perpendicular to the pressure roller) to guarantee the electrode is completely covered by the coating. Use a steel ruler to measure the length between marked points at the beginning and end of the electrode, estimating to 0.1mm, and record the length before compaction. After compaction, record the length between the corresponding marked points. Use (compacted length - uncompacted length) / uncompacted length as the electrode's elongation.
[0388] The test method for the number of flexible folds is as follows.
[0389] Cut the positive electrode sheet to 20×100mm. 2 Test the size of the sample; fold it in half with the front side facing up, flatten it with a 2kg roller, unfold it and check the gap against the light to see if light passes through. If no light passes through, fold it in half again with the back side facing up, flatten it with a 2kg roller, and check it against the light again. Repeat this process until light passes through the gap. Record the number of folds. Repeat the test three times and take the average value as the reference data for the flexibility of the electrode sheet.
[0390] 2. Energy density test
[0391] The lithium-ion secondary battery was left to stand at 25°C for 2 hours to ensure the battery temperature remained at 25°C. At 25°C, the battery was charged at 0.33C to the charging cutoff voltage of 3.65V, and then continued to be charged at this cutoff voltage under constant voltage until the current reached 0.05C, at which point charging was stopped (where C represents the rated capacity of the lithium-ion secondary battery). After leaving the battery to stand at 25°C for 1 hour, it was discharged at 0.33C at 25°C to the discharge cutoff voltage of 2.5V. The total discharge energy of the lithium-ion secondary battery was recorded as E0.
[0392] Measure the length, width, and height of the lithium-ion secondary battery, and calculate the volume value V0 of the lithium-ion secondary battery = length × width × height.
[0393] The volumetric energy density of a lithium-ion secondary battery = discharge energy of the lithium-ion secondary battery E0 / volume of the lithium-ion secondary battery V0.
[0394] 3. Cyclic performance testing method
[0395] At 25°C, the battery cells prepared in each embodiment and comparative example were charged at a constant current of 1C to 50% SOC, then charged at 0.87C to 80% SOC, and then charged at 0.33C to a cutoff voltage of 3.65V. Constant voltage charging was then continued at this cutoff voltage until the current reached 0.05C. Finally, constant current charging at 1C was performed until the discharge cutoff voltage reached 2.5V. This constitutes one charge-discharge cycle. The discharge capacity of the battery cell at this point is recorded as the discharge capacity E1 of the first cycle. This charging and discharging process was repeated until E2 = 0.8 × E1, and the number of cycles for the battery cell at this point was recorded.
[0396] Experimental parameters and test results
[0397] Batteries for each embodiment and comparative example were prepared according to the above method, and various performance parameters were measured. The results are shown in Tables 1, 2 and 3 below.
[0398] Table 1
[0399]
[0400]
[0401] Table 2
[0402]
[0403] Table 3
[0404]
[0405]
[0406] As can be seen from the data comparison of the embodiments and comparative examples, based on the total area of particles in the cross-section along the thickness direction of the positive electrode film, this application controls the area ratio of particles with particle size R1 satisfying 1.5μm≤R1<5μm to be 10.0%-20.0%, the area ratio of particles with particle size R2 satisfying 50nm≤R2<200nm to be 5.0%-12.0%, and the area ratio of particles with particle size R3 satisfying 200nm≤R3<1.5μm to be 73.0%-80.0%; the particle size concentration (D) of particles satisfying R3 is also considered. A90 -D A10 ) / D A50 The value is 1.40-1.683, which allows the battery to achieve a balance between energy density and cycle performance.
[0407] As can be seen from the comparison between Example 5 and other examples, the area ratio of particles with a particle size R1 satisfying 1.5μm≤R1<5μm is 13.00%-18.00%, which is beneficial for further increasing battery energy density. As can be seen from the comparison between Example 10 and other examples, the area ratio of particles with a particle size R1 satisfying 1.5μm≤R1<5μm is 13.00%-18.00%, which is beneficial for improving battery cycle performance.
[0408] As can be seen from the comparison between Example 8 and other examples, the area ratio of particles with a particle size R2 satisfying 50nm≤R2<200nm is 6.00%-10.00%, which is beneficial to improving the battery cycle performance. As can be seen from the comparison between Example 9 and other examples, the area ratio of particles with a particle size R2 satisfying 50nm≤R2<200nm is 6.00%-10.00%, which is beneficial to further improve the electrode compaction density and improve the battery energy density.
[0409] As can be seen from the comparison of Examples 4, 5, 10, 11 and other examples, the area ratio of particles with particle size R3 satisfying 200nm≤R3<1.5μm is 74.0%-78.0%, which is beneficial to further balance the relationship between electrode compaction density and battery energy density and cycle performance.
[0410] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A lithium-ion secondary battery, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive current collector and a positive electrode film disposed on at least one side of the positive current collector. The positive electrode film layer includes a positive electrode active material, which comprises lithium transition metal phosphate particles with at least a portion of their surface coated with carbon material. Based on the total area of particles in the cross-section along the thickness direction of the positive electrode film, the area ratio of particles with particle size R1 satisfying 1.5μm≤R1<5μm is 10.0%-20.0%, the area ratio of particles with particle size R2 satisfying 50nm≤R2<200nm is 5.0%-12.0%, and the area ratio of particles with particle size R3 satisfying 200nm≤R3<1.5μm is 73.0%-80.0%. Particle size distribution (D) of particles whose size satisfies R3 A90 -D A10 ) / D A50 The range is 1.40-1.
683.
2. The lithium-ion secondary battery according to claim 1, characterized in that, The area ratio of particles with a particle size R3 satisfying 200nm≤R3<1.5μm is 74.0%-78.0%.
3. The lithium-ion secondary battery according to claim 1 or 2, characterized in that, The area percentage of particles with a particle size R2 satisfying 50nm≤R2<200nm is 6.00%-10.00%.
4. The lithium-ion secondary battery according to any one of claims 1 to 3, characterized in that, The area percentage of particles with a particle size R1 satisfying 1.5μm≤R1<5μm is 13.00%-18.00%.
5. The lithium-ion secondary battery according to any one of claims 1 to 4, characterized in that, In the cumulative distribution curve of the spheroidal area of the particles obtained from the cross-section of the positive electrode film along the thickness direction of the electrode sheet, the median L of the spheroidality is... A50 The value is 0.70-0.85, and can be selected as 0.70-0.
76.
6. The lithium-ion secondary battery according to any one of claims 1 to 5, characterized in that, In the cumulative distribution curve of the spheroidal area of particles with a particle size R1 satisfying 1.5μm≤R1<5μm obtained from the cross-section of the positive electrode film along the electrode thickness direction, the median L of the spheroidality is... R1A50 It is 0.70-0.
76.
7. The lithium-ion secondary battery according to any one of claims 1 to 6, characterized in that, In the cumulative distribution curve of the spheroidal area of particles with a particle size R2 satisfying 50nm ≤ R2 < 200nm obtained from the cross-section of the positive electrode film along the electrode thickness direction, the median L of the spheroidality is... R2A50 It is 0.73-0.
80.
8. The lithium-ion secondary battery according to any one of claims 1 to 7, characterized in that, In the cumulative distribution curve of the spheroidal area of particles with a particle size R3 satisfying 200nm ≤ R3 < 1.5μm obtained from the cross-section of the positive electrode film along the electrode thickness direction, the median L of the spheroidality is... R3A50 It is 0.71-0.
77.
9. The lithium-ion secondary battery according to any one of claims 1 to 8, characterized in that, In the cumulative roughness area distribution curve of the particles obtained along the thickness direction of the positive electrode film, the median R of the particle roughness is... A50 It is 0.92-0.
96.
10. The lithium-ion secondary battery according to any one of claims 1 to 9, characterized in that, In the cumulative distribution curve of the graphitization degree C value of the positive electrode film obtained in the laser microscopy confocal Raman spectroscopy instrument scanning mode, the median C of the graphitization degree is... 50 The value is 0.98-1.20, and can be selected as 1.02-1.10, where the graphitization degree C value is I. G / I D I G This indicates that the Raman spectrum is at 1580±100 cm⁻¹ -1 The intensity of peak G at I D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.
11. The lithium-ion secondary battery according to any one of claims 1 to 10, characterized in that, In the cumulative distribution curve of the coating value B obtained by laser microscopy confocal Raman spectroscopy in instrument scanning mode, the median B of the coating value is... 50 The value is 0.30-0.50, where the coating value B is I. P / I D , where I P This indicates that the Raman spectrum is at 948±100 cm⁻¹ -1 The intensity of the P peak at I D This indicates that the Raman spectrum is at 1350±100 cm⁻¹ -1 The intensity of peak D at that location.
12. The lithium-ion secondary battery according to any one of claims 1 to 11, characterized in that, Based on the total mass of the positive electrode active material, the carbon content is 0.8%-1.8%, optionally 0.90%-1.5%.
13. The lithium-ion secondary battery according to any one of claims 1 to 12, characterized in that, The lithium iron ion site defect concentration of the positive electrode active material is 0.001%-1.5%, and can be optionally 0.01%-1.0%.
14. The lithium-ion secondary battery according to any one of claims 1 to 13, characterized in that, The lithium-containing transition metal phosphate particles comprise components having the following general formula: The m Fe x P y O j Q q , Wherein, Q includes one or more of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, and Br, 0.8≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0<q≤0.
1.
15. The lithium-ion secondary battery according to any one of claims 1 to 14, characterized in that, The positive electrode active material includes one or more of lithium iron phosphate and its doped and modified materials, and coated and modified materials.
16. The lithium-ion secondary battery according to any one of claims 1 to 15, characterized in that, The positive electrode active material includes titanium, and the mass content of titanium is 4000ppm-8000ppm based on the total mass of the positive electrode active material.
17. The lithium-ion secondary battery according to any one of claims 1 to 16, characterized in that, The tap density of the positive electrode active material is 1.00 g / cm³. 3 -1.70g / cm 3 1.20g / cm³ is an optional value. 3 -1.50g / cm 3 ; and / or the compacted density of the positive electrode active material under 3T pressure is 2.55 g / cm³. 3 -2.70g / cm 3 The option is 2.58g / cm³. 3 -2.68g / cm 3 .
18. The lithium-ion secondary battery according to any one of claims 1 to 17, characterized in that, The resistivity of the positive electrode active material at 8 MPa pressure is 0.5 Ω·cm-60.0 Ω·cm, and can be selected as 2.0 Ω·cm-40.0 Ω·cm.
19. The lithium-ion secondary battery according to any one of claims 1 to 18, characterized in that, The discharge capacity of the positive electrode active material at a 1C discharge rate is 135mAh / g-150mAh / g.
20. The lithium-ion secondary battery according to any one of claims 1 to 19, characterized in that, The discharge capacity percentage η of the positive electrode active material discharged to 3.2V is ≥85%. η is defined as follows: at room temperature, a coin cell containing the positive electrode active material is charged and discharged twice at a constant current rate of 0.1C within a voltage range of 2.0V to 3.75V, followed by a constant current charge and discharge once at a constant current rate of 1C. In the 1C charge and discharge test, the capacity value extracted at a discharge voltage of 3.2V is recorded as C1, and the capacity value extracted at a discharge voltage of 2.0V is recorded as C2. η = C1 / C2. The charging process includes constant voltage charging at a constant voltage of 3.75V and a constant voltage cutoff current of 50μA.
21. The lithium-ion secondary battery according to any one of claims 1 to 20, characterized in that, The positive electrode film also includes a conductive agent, and the mass content of the conductive agent is 0.01%-1.5% based on the total mass of the positive electrode film.
22. The lithium-ion secondary battery according to any one of claims 1 to 21, characterized in that, The positive electrode film layer also includes a binder. Based on the total mass of the positive electrode film layer, the mass content of the positive electrode active material is 92%-99.5%, optionally 96.5%-99.5%; the mass content of the binder is 0.5%-3%.
23. The lithium-ion secondary battery according to any one of claims 1 to 22, characterized in that, The single-sided density of the positive electrode film is 300 mg / 1540 mm². 2 -450mg / 1540mm 2 .
24. The lithium-ion secondary battery according to any one of claims 1 to 23, characterized in that, In the fully discharged state, the compaction density of the positive electrode film in the lithium-ion secondary battery is 2.52 g / cm³. 3 -2.78g / cm 3 .
25. The lithium-ion secondary battery according to any one of claims 1 to 24, characterized in that, In the fully discharged state, the positive electrode film of the lithium-ion secondary battery has a compaction density of 2.55 g / cm³. 3 -2.75g / cm 3 .
26. The lithium-ion secondary battery according to any one of claims 1 to 25, characterized in that, The positive electrode film layer satisfies at least one of the following conditions: (1) In the fully discharged state, the compaction density of the positive electrode film of the lithium-ion secondary battery is 2.52 g / cm³. 3 -2.78g / cm 3 In the cross-section along the thickness direction of the electrode sheet, the porosity of the positive electrode film is 10%-22%. (2) In the fully discharged state, the positive electrode film of the lithium-ion secondary battery has a compaction density of 2.55 g / cm³. 3 -2.75g / cm 3 In the cross-section along the thickness direction of the electrode sheet, the porosity of the positive electrode film is 10%-20%.
27. The lithium-ion secondary battery according to any one of claims 1 to 26, characterized in that, The positive electrode sheet includes a base coating layer, which is disposed between the positive electrode film layer and the positive electrode current collector; the base coating layer satisfies at least one of the following conditions: (1) The base coating includes carbon-based particles, and the distribution density of carbon-based particles with a particle size greater than 100 nm in the base coating is ≤10 pcs / 10 μm; (2) The compacted density of the positive electrode sheet in its fully loaded state is greater than or equal to 2.4 g / cm³. 3 The thickness of the base coating on one side is 1μm-4μm; (3) The compacted density of the positive electrode sheet in its fully loaded state is greater than or equal to 2.5 g / cm³. 3 The thickness of the base coating layer on one side is 2μm-4μm.
28. A battery device, characterized in that, The battery device includes any one of claims 1 to 27, wherein the battery device comprises at least one of a battery module, a battery pack, and an energy storage battery.
29. An electrical appliance, characterized in that, Includes the lithium-ion secondary battery according to any one of claims 1 to 27 or the battery device according to claim 28.
30. A method for preparing a positive electrode active material, characterized in that, The preparation method includes: obtaining a first positive electrode active material component and a second positive electrode active material component; mixing the first positive electrode active material component and the second positive electrode active material component, adding a carbon source, and obtaining a mixed positive electrode active material component; subjecting the mixed positive electrode active material component to a third sintering to obtain a sintered product, and crushing the sintered product to obtain a positive electrode active material; wherein, the D of the first positive electrode active material component is... V50 The D of the second positive electrode active material component is 0.35μm-0.45μm. V50 The thickness is 0.25μm-0.35μm, and the mass ratio of the first positive electrode active material component to the second positive electrode active material component is (60:40)-(70:30).
31. The preparation method according to claim 30, characterized in that, The preparation method of the first positive electrode active material includes: obtaining a first mixed raw material comprising a first carbon source, a first lithium source, a first iron source, a first phosphorus source and a solvent; grinding the first mixed raw material to obtain a first mixed slurry; drying the first mixed slurry to obtain a first precursor powder; and subjecting the first precursor powder to a first sintering to obtain the first positive electrode active material; wherein the atomic molar ratio of iron to phosphorus in the first mixed raw material is 0.95-1; and the sintering temperature is 765℃-795℃.
32. The preparation method according to claim 30 or 31, characterized in that, The preparation method of the second positive electrode active material includes: obtaining a second mixed raw material comprising a second carbon source, a second lithium source, a second iron source, a second phosphorus source and a solvent; grinding the second mixed raw material to obtain a second mixed slurry; drying the second mixed slurry to obtain a second precursor powder; and subjecting the second precursor powder to a second sintering to obtain the second positive electrode active material; wherein the sintering temperature is 705℃-735℃.
33. A method for preparing a positive electrode sheet, characterized in that, The preparation method includes sequentially adding a binder, a conductive agent, and the positive electrode active material prepared by the preparation method according to any one of claims 30 to 32, dry mixing them, adding a solvent, stirring, adjusting the viscosity, and obtaining a slurry; transferring the slurry to at least one side of the positive electrode current collector, drying, and hot pressing to obtain a positive electrode film layer.
34. The preparation method according to claim 33, characterized in that, The viscosity of the shipped slurry is 8000 Pa·s-12000 Pa·s.
35. The preparation method according to claim 33 or 34, characterized in that, The hot pressing includes at least three hot roller pressings, with the hot roller pressure increasing sequentially to 20-50 tons, 50-70 tons, and 70-90 tons; the hot roller temperature is 40℃-80℃. Before the first hot roller compaction, the positive electrode sheet is heated to a temperature of 40℃-50℃.
